Computational electromagnetic geophysics for groundwater system studies: A review of established practices and recent advances - Paula Rulff; Octavio Castillo-Reyes; Wouter Deleersnyder; Maria Carrizo Mascarell; Burke J. Minsley; Jude King (Journal of Hydrology, 2026)

From green extraction to clean-label formulation: natural deep eutectic solvents as multifunctional extraction–formulation systems for agri-food valorization - Clara Gomez-Urios; Mario Paños-Huertas; Ines Castillo-Esteve; Clara Cortes; Jesus Blesa; Maria J. Esteve (Food Research International, 2026)

Valorization of marine sargassum biomass through in situ spectroscopic analysis for potential sodium-ion battery anode applications - Gabriela J. Rojas-Castillo; J. Silvestre Mendoza-Figueroa; J. Marcos Esparza-Schulz; Luis Lartundo Rojas; Guadalupe Ramos-Sánchez (Biomass and Bioenergy, 2026)

Centennial-scale climate variability and human land-use shaped vegetation and lake dynamics in southern Spain over the past three millennia - Gonzalo Jiménez-Moreno; Erik J. de Boer; Jon Camuera; Antonio García-Alix; Fernando Gázquez; Aurora Castillo-Baquera; Lucía Martegani; Miguel Rodríguez-Rodríguez; Marta Rodrigo-Gámiz; Francisco J. Jiménez-Espejo; Lu Chenao; José S. Carrión (Anthropocene, 2026)

Labour regimes and farm diversity in greenhouse farming systems: evidence from Mediterranean Europe - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña (Journal of Rural Studies, 2026)

Lethal and sublethal effects of Alexandrium affine and Alexandrium pseudogonyaulax on juveniles of the Pacific oyster Magallana gigas - Ismavy C. Castillo-Quintana; Ignacio Leyva-Valencia; Christine J. Band-Schmidt; Pedro Cruz-Hernández; María del Carmen Rodríguez Jaramillo; José Luis Ramírez Arce (Harmful Algae, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

Spatial Partitioning of Microbial Functional Potential Suggests Complex Nitrogen Cycling in a Subterranean Estuary - Daniel Romano‐Gude; Nestor Arandia‐Gorostidi; Catalina Mena; Marc Diego‐Feliu; Bella Almillategui; Anna J. Székely; Stefan Bertilsson; Andrea G. Bravo; Jesus Carrera; Cristina Romera‐Castillo; Albert Folch; Jordi Garcia‐Orellana; et al. (Environmental Microbiology, 2026)
Subterranean estuaries (STEs) are key bioreactors regulating the quantity and chemical composition of groundwater‐derived nitrogen (N) reaching coastal ecosystems. Yet, the microbial controls on N‐cycling within these groundwater–seawater mixing zones remain poorly understood. We investigated the spatio‐temporal variations in microbial communities and their N‐cycling potential within an alluvial Mediterranean STE with high N concentration. We explored changes in microbial abundance, heterotrophic activity, taxonomic composition, and the abundance of N‐cycling genes across groundwater samples collected at several depths and distances from the shoreline in winter and summer. Microbial abundance, activity, and diversity varied strongly across hydrochemical zones according to physicochemistry and aquifer depth but showed limited seasonality. Functional predictions suggested a complex, spatially structured suite of N pathways encoded by diverse taxa occupying different STE zones, and quantitative‐PCR revealed niche partitioning between ammonia‐oxidizing archaea, prevalent in fresh‐groundwater, and bacterial denitrifiers enriched in deep‐saline layers. Multiple linear model predictions showed a stronger fit for NO 2 − and NH 4 + concentrations when using microbial properties than when using environmental variables, highlighting their importance for understanding N cycling in STEs. Our results suggest that the functional potential of the STE microbiome is complex and spatially structured across hydrochemical zones, explaining spatial variations in STE N‐cycling.

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

A comprehensive approach to the in vitro propagation of Vanilla planifolia Andrews: evaluation of different cytokinins and symbiosis with a mycorrhizal fungus - Gabriela García-Vázquez; Antonia Gutiérrez-Mora; J. Francisco Castillo-Esparza; Adrián Alejandro Hernández-Sánchez; Carolina Madero-Vega; Guillermo Ángeles; Gloria Carrión; Martín Mata-Rosas (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Prediction of Adverse effects of Geomagnetic storms and Energetic Radiation (PAGER) project - Yuri Y. Shprits; Tony Arber; Michael Liemohn; Ondřej Santolík; Keith Bennett; Stefano Bianco; Melanie Burns; Angelica Castillo; Marina García Peñaranda; Bernhard Haas; Julia Himmelsbach; Artem Smirnov; et al. (Advances in Space Research, 2026)

LA-COMET group: In vivo application of the comet assay in animal and plant models, including wild species - Gisela L. Poletta; Patricia Mussali-Galante; J. Alfredo Castillo-Ipiña; Guillermo Espinosa-Reyes; Ana Rosa Flores-Márquez; Donaji J. González-Mille; César A. Ilizaliturri-Hernández; Celeste Ruiz de Arcaute; Efraín Tovar-Sánchez; Juliana da Silva; Deidamia Franco; Ana Leticia García; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.

Vaccine strategies for cancer prevention in Lynch syndrome: the potential of dendritic cell-based therapy - Romy N. Kuipers; Mark A. J. Gorris; Cristina Bayó; Tom Hofland; Daniel Benítez Ribas; Georgina Flórez Grau; Nicoline Hoogerbrugge; Joaquin Castillo; Francesc Balaguer; Tanya M. Bisseling; Gerty Schreibelt; I. Jolanda M. de Vries (Familial Cancer, 2026)
Cancer vaccines offer a promising strategy for cancer prevention, particularly in hereditary cancer syndromes such as Lynch syndrome (LS). LS is characterized by a high lifetime risk of developing various malignancies due to defects in DNA mismatch repair, leading to an accumulation of mutations, particularly frameshift insertion/deletions (indels) within microsatellite loci. These indels create shared tumour-specific neoantigens, which are unique to LS and can be recognized by the immune system and trigger cancer cell killing. Importantly, these neoantigens are also present in precancerous lesions, making LS an ideal target for immune-interception strategies aimed at prevention. Over the years, a variety of vaccine designs targeting different antigens along with a range of delivery platforms have been explored for different types of tumours, each with its own advantages and limitations. In this review, we provide an overview of the key antigens and delivery platforms used in cancer preventive vaccine development for LS, evaluate their limited clinical outcomes to date, and explore the future directions of preventive vaccine immunotherapy. A particular focus is placed on the promising potential of dendritic cell vaccination therapy as a future approach in this field.

Lactic acid spraying on split carcasses reshapes microbial succession and reduces the occurrence of blown pack spoilage in vacuum-packaged beef stored at different temperatures over extended shelf life - Sávio Sandes; Naiara Figueiredo; Sumaia Pires; Debora Assis; Silvia Pedroso; Maria José Paiva; Elisabeth Neumann; Veronica O. Alvarenga; Carmen J. Contreras-Castillo; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Landslides impact and management on human settlements over 3000 years: the case of the Montilla Castle Hill (Córdoba, Spain) - Francisco J. Jiménez-Espejo; Lourdes González-Castillo; Francisco Lamas; Francisco José Martínez-Moreno; Jesús Galindo-Zaldívar; Jon Camuera; Sergio Moyano; José A. Peláez; José Luis Urbano; Mónica Camacho Calderón; Raimundo Ortiz (Natural Hazards, 2026)
In recent decades, global urbanisation has increased dramatically. The study of urbanised areas over the last millennium offers valuable insight into the long-term landslide hazards associated with human settlements. Anthropogenic environmental impact and urbanisation in southern Iberia began around 2200 yr BCE, rendering this region a unique location to examine interactions between building construction and landslide over millennial timescales. The Montilla Castle Hill, in south Spain, was selected for this study due to its clear evidence of landslides and confirmed historical occupation dating back to the Copper Age. This study adopted a multidisciplinary approach, integrating archaeology, geology, geophysics, geotechnical modelling and related disciplines to characterize construction types and pathologies, as well as landslide ages, critical stability threshold values, landslide mechanisms and key features. The obtained data were compared with regional paleoclimate records and earthquakes/tsunamic events in south Iberia. Four landslide activity phases have been dated: from 650–550 BCE, from 400 to 200 BCE, from 1400 to 1450 and along the XVIII to XX centuries. Observations revealed that the presence of major buildings at the summit of the Castle Hill, at the landslide crown, were a key factor in promoting the reactivation of ancient landslides. This study found no evidence linking climate conditions with slope stability, but a correlation with major regional earthquakes was observed, in agreement with the modelled values obtained.

Temperature and photoperiod interactions influence the cessation of wood growth in three temperate and boreal conifers - Jianhong Lin; Cyrille B.K. Rathgeber; Patrick Fonti; Sergio Rossi; Henri Cuny; Edurne Martinez del Castillo; Katarina Čufar; J. Julio Camarero; Alessio Giovannelli; Harri Mäkinen; Peter Prislan; Walter Oberhuber; et al. (Agricultural and Forest Meteorology, 2026)

Environmental Gradients Decouple Demographic and Adaptive Connectivity in a Highly Mobile Coastal Marine Species - Chris J. Brauer; Andrea Bertram; Jonathan Sandoval‐Castillo; Anthony Fowler; Justin D. Bell; Paul Hamer; Maren Wellenreuther; Luciano B. Beheregaray (Molecular Ecology, 2026)
Understanding how eco‐evolutionary processes shape genetic variation and persistence in marine species with highly variable recruitment dynamics and dispersal potential remains a fundamental challenge, particularly when considering the interplay between gene flow and local adaptation. Here, we employed a seascape genomics approach to investigate population connectivity and local adaptation in Australasian snapper ( Chrysophrys auratus , Sparidae) along 1500 km of the environmentally heterogeneous southern Australian coastline. Using genome‐wide SNPs, we identified distinct eastern and western regional populations aligned with known biogeographical regions. Genotype‐environment association analyses revealed 855 candidate adaptive loci associated with environmental variation, including temperature, salinity and primary productivity. Connectivity analyses using neutral markers indicated high gene flow within both eastern and western regions, while candidate adaptive loci revealed substantially reduced connectivity, especially for Northern Spencer Gulf and West Coast populations. This contrast implies a decoupling of demographic and adaptive connectivity, in which strong environmental gradients appear to reduce the effective exchange of adaptive variation despite high overall connectivity. Our results support contingent migration as a potential mechanism modulating the balance between local adaptation and gene flow in this economically and ecologically important marine species. These findings might also have implications for regional management of other coastal fisheries that are experiencing substantial declines. As climate change alters coastal marine environments around the world, the dynamics of local recruitment, site fidelity and local adaptation are expected to change. This highlights the importance of integrating knowledge about eco‐evolutionary processes into marine resource management, fisheries stock assessment, and restocking and stock enhancement activities.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Diagnosing the governance gap: Technically informed public perception and institutional trust in microplastic regulation in Costa Rica - José Roberto Vega-Baudrit; Yendry Corrales; Karla J. Merazzo; Badr Bahloul; Luis Castillo-Henríquez; Hannia León (Marine Policy, 2026)

Using front face fluorescence for rapid estimation of furosine concentration in heat treated milk: a kinetic study - C. González-Gallardo; N. Ayala; F. Ali; A. Zamora; J. Saldo; M. Castillo (International Dairy Journal, 2026)

Metabolic and productive responses to heat stress in transition dairy cows: Interactions with calving stage, season, and farm management - E. N. Martínez; C. Castillo; L. Avendaño Reyes; Rodrigo Muiño; L. Díaz-González; J. L. Benedito; J. Hernández (International Journal of Biometeorology, 2026)
This study investigated the effects of heat stress (HS), calving period, and farm-level management on the metabolic and productive responses of transition dairy cows. Conducted on three commercial farms in northwestern Spain, the study employed a multifactorial design across two seasons (winter and summer) and four peripartum time points. Biochemical parameters, including non-esterified fatty acid (NEFA), β-hydroxybutyrate (BHB), urea, total protein, albumin, glucose, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (ASAT) were analyzed using repeated-measures MANOVA. No significant three-way interactions were found, but several two-way interactions emerged. Notably, NEFA and urea levels varied significantly between farms, while total protein and albumin were influenced by both partum stage and season. Elevated NEFA and BHB concentrations postpartum indicated intensified lipid mobilization and negative energy balance, exacerbated under HS. Reduced albumin and increased urea levels suggested hepatic stress and altered protein metabolism. Farm-specific differences in ASAT during summer highlighted the role of local environmental and management conditions. These findings underscore the complex interplay between physiological stage, environmental stressors, and farm practices. Tailored intervention (such as nutritional adjustments, cooling systems, and precision monitoring) are essential to mitigate the metabolic burden of HS and safeguard cow health and productivity. Future research should explore long-term impacts and adaptive strategies across diverse production systems.

Ecological geography of the hawksbill turtle (Eretmochelys imbricata) in the West Atlantic - Peter Meylan; F. Alberto Abreu-Grobois; Anne Meylan; Beth Brost; Whitney Bullock; Genaro Castillo; Liza J. Conrad; Denise Flaherty; Arcelio Gonzalez Hooker; Jennifer Gray; Cristina Ordoñez; Sue Schaf; et al. (Frontiers in Marine Science, 2026)
Understanding the geographic distribution of genetic diversity of imperiled species across all life history stages, and identifying the factors that shape those distributions, are key to maintaining long-term genetic diversity and the health of populations. This knowledge is particularly important for highly mobile marine organisms, whose extensive movements can obscure patterns of population structure. We substantially expand the genetic dataset for the critically endangered hawksbill turtle, Eretmochelys imbricata , in the West Atlantic, focusing on the southwest Caribbean. Our dataset comprises nearly 3,000 mtDNA control region sequences (740 bp) assigned to 60 haplotypes: 41 found in rookeries and 47 in foraging grounds, including 17 orphan haplotypes. The Panama metapopulation represents a major center of genetic diversity for hawksbills, with one of the highest recorded diversity values for the species ( h = 0.749, π = 0.00782), nine endemic haplotypes, and four additional haplotypes that are endemic to the Southwest Caribbean. Rarefaction analyses indicate that a sample size of at least 100 is necessary to reveal true haplotype richness at most rookeries. Many-to-many mixed stock analyses, which incorporated rookery size and distance priors for 19 rookeries and 15 developmental foraging grounds, suggest that hatchlings from rookeries in the southwest Caribbean are distributed among multiple, widely-spaced foraging grounds across the West Atlantic. These results support a groups-to-soups analogy, in which genetic variability across foraging grounds represents a continuum of genetic diversity that can best be explained by a “current conveyor” model. The dataset shows that philopatry in hawksbills is not absolute, resulting in true biological dispersal and geneflow on local, regional, and ocean-basin scales, likely facilitated by dispersion during the epipelagic stage. The important contribution of oceanographic features to genetic variation at rookeries and foraging grounds is corroborated, as is the concept of oceanographic “dispersal shadows” that limit geneflow between rookeries. This study reinforces the assertion that all range states share responsibility for the recovery of the hawksbill, because foraging grounds, that are often at distant locations, are the source of future generations of reproductive adults. We also document significant movement by hawksbills between regional management units (RMUs) 29 and 30 in the West Atlantic. The Spanish version of the Abstract is available in Supplementary File 1 .

Light sensing in fish embryonic cells: A circadian analysis of visual and non-visual opsin expression using a seabream embryonic stem cell line - Alba Vergès-Castillo; Patricia Herrera-Pérez; Carlos Pendón; Jaume Pérez-Sánchez; Águeda J. Martín-Robles; José A. Muñoz-Cueto (Aquaculture, 2026)

Microbial consortia in mine water bioremediation: principles, design and practical applications - A. Matu; A. Valverde; E. Cason; A. Gomez-Arias; M. Maleke; J. Castillo (Water Research, 2026)

Process optimization and techno-economic analysis of polyethylene terephthalate (PET) depolymerization in a non-aqueous alkaline environment for monomer recovery and reuse - Aakash Chakraborty; Damián J. Castillo-Preciado; Beza Moges; Zannat Mahal; Kang Kang; Arturo Sanchez; Sudip K. Rakshit (Waste Management, 2026)

Arabidopsis trehalose phosphate synthaseII (tpsII) mutants are ABA-hypersensitive during early development while tps7 to tps11 show increased drought susceptibility consistent with anomalous stomatal closure and weak post-stress recovery responses - Daniela J. Bonilla-Córdoba; Andrea C. Ruiz-Castillo; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; Lino Sánchez-Segura; John Délano-Frier (Plant Science, 2026)

Pigments, Chromatophore Structure, and Gene Expression Underlying Colour Polytypy of a Panamanian Poison Frog - Vasiliki Mantzana‐Oikonomaki; Giselle Tamayo‐Castillo; Víctor Vásquez‐Cháves; Abel Mora‐Machado; William J. Zamora Ramirez; Roberto Ibáñez; Heike Pröhl; Ariel Rodríguez (Molecular Ecology, 2026)
Colour polytypism represents an example of phenotypic diversification shaped by genetic divergence and ecological pressures. Poison frogs of the genus Oophaga (Dendrobatidae) are highly polytypic in coloration, making them an ideal system for investigating the genetic and physiological basis of colour variation. We examined gene expression, pigment and histological differences across four colour morphs (aquamarine, brown, green, and red) of Oophaga vicentei from mainland Panama. RNA sequencing revealed 1838 and 5085 differentially expressed genes (DEGs) in the skin and liver, respectively. Melanin synthesis genes were upregulated in the brown morph, whereas pteridine pathway genes were upregulated in red and green morphs, consistent with previous findings in O. pumilio . In aquamarine frogs, pigment composition was similar to brown and green frogs, but transcriptional profiles were highly divergent. Red morphs upregulate a paralog of the dendrobatid ketolase cyp3a80 in the liver, suggesting modified ketolation mechanisms in O. vicentei . This is consistent with higher ketocarotenoid accumulation in red frogs. Co‐expression network analysis identified morph‐related modules in both tissues but the relationship between modules and known pigmentation pathways remains unclear. Comparative analysis across seven dendrobatid species revealed conserved pigmentation genes (e.g., xdh , ttc3b ) alongside morph‐specific expression patterns. Our results show that red frogs are dissimilar in pigments, chromatophore structure, and gene expression, whereas aquamarine, brown, and green coloration share overlapping pigment profiles and chromatophore organisation, with transcriptional differences suggesting structural or regulatory mechanisms.

Trace metal contamination along an estuarine gradient under increasing anthropogenic pressure: A case study from the Guadalquivir estuary (SW Iberian Peninsula) - I. Donázar-Aramendía; C. Megina; J.M. Miró; J. Martín-Gallardo; J.M. Castillo; J.C. García-Gómez (Marine Pollution Bulletin, 2025)

Reducing NaCl in beef burgers using ultrasound and micronized salt: Effects on hedonic and sensory perception, technological, and textural characteristics - Chimenes Leal de Araújo; Milagros Maribel Coaguila Gonza; Monique Marcondes Krauskopf; Paulo Renan Carvalho Afo Navarro; Joel Takeshi Matsuura; Karoline Costa Santos; Fernanda Papa Spada; Severino Matias de Alencar; Erick Saldaña; Carmen J. Contreras Castillo (Food Research International, 2025)

Three Non-Invasive Tests Reveal Anxiety-like Responses During Food Anticipation in Rainbow Trout - André Barany; Miguel Gómez-Boronat; Lisbeth Herrera-Castillo; María J. Delgado; Nuria de Pedro; Ana M. Larrán; Esther Isorna (Fishes, 2025)
Anxiety-like behavior in fish is commonly assessed using non-invasive behavioral paradigms such as the Light/Dark preference, Novel Tank, and Open Field tests. In this study, we validated these three assays in rainbow trout (Oncorhynchus mykiss), a species of commercial relevance, to characterize their anxiety-related responses. To explore behavioral changes associated with feeding anticipation and satiety, we implemented a feeding schedule consisting of two daily meals and conducted behavioral tests at specific times before and after feeding. Trout exhibited clear patterns of scototaxis, geotaxis, and thigmotaxis, consistent with anxiety-like behavior described in other teleosts. Our results showed a significant increase in anxiety-like responses before feeding, coinciding with food anticipatory activity observed prior to expected feeding schedules, which diminished after food intake, as evidenced by each test individually. Moreover, multivariate analysis combining parameters from all three tests improved discrimination between anxious and relaxed fish. The behavioral states before and after feeding resembled anxiety-like and anxiolytic conditions reported in other species, supporting that food anticipatory activity reflects an anxious state in rainbow trout as well. These findings endorse using a multi-test behavioral battery to assess anxiety-like states and provide a framework for studying neurobiological mechanisms of emotional regulation related to feeding in teleosts.

Recovery of strategic elements from mining tailings at La Cienega, Peru, through geochemical and mineralogical assessment: a focus on circular economy policy - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge Chira-Fernandez; Cesar De la Cruz-Poma; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

Bridging yield gaps in rice production through integrated crop and nutrient management with farmer groups - Hasil Sembiring; Setia Sari Girsang; Arif Anshori; Erythrina Erythrina; Pepi Nur Susilawati; Andy Bhermana; Yohanis Ngongo; Sidiq Hanapi; Darojat Prawiranegara; Nuning A. Subekti; Priatna Sasmita; Irish Lorraine B. Pabuayon; et al. (Field Crops Research, 2025)

Phenolic compounds and epigenetic mechanisms regulating gene expression: effects on human health - Silvia Lorente-Cebrián; André G. V. Costa; J. Andrés Castillo-Rivas; Marta Castro; José Miguel Arbonés-Mainar; Saioa Goñi; Sara Remón; Paula Aranaz; Víctor López; Inmaculada Martín-Burriel; Fermín I. Milagro (Journal of Physiology and Biochemistry, 2025)
Phenolic compounds are a large class of phytochemicals with relevant physiological effects that are naturally found in plant-origin foods and derived products. Beneficial effects associated with polyphenol consumption are related to their ability to prevent and/or counteract disease features: they exert anti-inflammatory, antioxidant and anticancer effects, as well as protective actions against metabolic diseases. Phenolic compounds and their metabolites can modulate cell function by regulating gene expression. These effects are partially mediated through specific changes in epigenetic mechanisms such as DNA methylation, histone modifications and microRNA (miRNA) expression. Some polyphenols affect DNA methylation and are effective in counteracting deleterious actions induced by inflammatory/pro-oxidant factors, both in in vitro and in vivo settings. Specific mechanisms include modulation of methyl-transferases, whose levels are inhibited upon polyphenols treatment. Some polyphenols are histone deacetylase inhibitors, which prevent transcriptional repression and suppress tumor and inflammation genes by affecting selective regulation of miRNA expression. Their mostly recognized actions as anti-inflammatory and antioxidants seem to be partially mediated through regulation of individual miRNAs. Due to these actions, polyphenols and polyphenol-derived metabolites are under study in clinical and interventional trials for their benefits on inflammation and/or metabolic disorders. In conclusion, phenolic compounds might be an interesting approach to contribute to human homeostasis given their capacity to dynamically regulate epigenetic factors at cellular and systemic level. The present review aims to study available evidence regarding regulatory effects of polyphenols on gene expression, specifically mediated through epigenetic mechanisms.

Strategic potential assessment of lanthanum and scandium through geochemical-lithological analysis with unsupervised machine learning in southern Ecuador - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; José A. Guartán; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Resources Policy, 2025)

A recently identified mass-transport deposit stack in the Guaymas Basin, Gulf of California (México), and its implication in the basin tectonics - A. Piña; J. Stock; D. Lizarralde; S. Hart; K. Marsaglia; C. Gallegos-Castillo; C. Berndt; A. González-Fernández; C. Mortera-Gutiérrez; A. Martín-Barajas (Marine Geology, 2025)

Nutrition Assessment in Cyclic Vomiting Syndrome: Exploring the Prevalence of Avoidant/Restrictive Food Intake Disorder, Disordered Eating, and Metabolic Dysregulation - L. Forsthoefel; G. Vanhouwe; O. Khan; K. Heitman; K. Goheen; E. Holley; P. Madril; J. Kennel; R. Jimenez-Castillo; S. Arumugam; M. Vyas; P. Goday; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Microbial diversity and biogeochemical potential related to C and N coupling in the oxygen minimum zone in a warming scenario - Patricia M. Valdespino-Castillo; Andrea Bautista-García; Rocío J. Alcántara-Hernández; Mariel Barjau-Aguilar; Fabio Favoretto; Fermín S. Castillo-Sandoval; Luz Ma. López-Gómez; Andrea P. Guzmán-Arias; Alex González; Nancy Calisto-Ulloa; Hiram Rosales-Nanduca; Anidia Blanco-Jarvio; et al. (Journal of Marine Systems, 2025)

Geochemical and mineralogical characterization of critical elements in gold tailings from the La Cienega, Peru, and assessment of their reuse potential - Marco A. Cotrina-Teatino; Jairo J. Marquina-Araujo; Jose N. Mamani-Quispe; Jorge E. Chira-Fernandez; Aldo R. Castillo-Chung; Solio M. Arango-Retamozo; Joe A. González-Vasquez; Salomon M. Ortiz-Quintanilla (Journal of Environmental Chemical Engineering, 2025)

Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.

Hyperthermia and Early Growth of Cerebral Infarct: The Potential Role of Blood–Brain Barrier Permeability - Crhistian-Mario Oblitas; Ana Sampedro-Viana; Sabela Fernández-Rodicio; Manuel Rodríguez-Yáñez; Iria López-Dequidt; Arturo Gonzalez-Quintela; Antonio J. Mosqueira; Jacobo Porto-Álvarez; Javier Martínez Fernández; Marcos Bazarra-Barreiros; María Teresa Abengoza-Bello; Sara Ortega-Espina; et al. (Translational Stroke Research, 2025)
Hyperthermia within the first 24 h following ischemic stroke (IS) has been associated with poor outcomes. We sought to determine whether blood–brain barrier (BBB) permeability contributes to the relationship between hyperthermia and early infarct growth (EIG). A retrospective analysis was conducted on a prospective stroke biobank. EIG was defined as the percentage difference between the initial volume (mL) determined by the diffusion-weighted imaging at admission and the volume (mL) from the control CT image on the 4 th–7 th day. Hyperthermia was defined as an axillary body temperature ≥ 37.5 °C within the first 24 h. Soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) serum levels were measured by ELISA. One-hundred and two (19.7%) patients showed EIG from a cohort of 519 patients (45.6% females). Linear correlation was observed for axillar body temperature and EIG (Pearson’s r = 0.46; p < 0.001). sTWEAK serum levels showed a c -statistic of 0.74 (95% CI: 0.69–0.79), with an optimal cut-off point > 3000 pg/mL for EIG prediction. Moreover, microalbuminuria levels strongly correlated with sTWEAK levels (Pearson’s r = 0.75; p < 0.001). In the multivariate analysis for EIG was observed an independent association with hyperthermia (adjusted OR 24.21; 95% CI: 12.03–39.12), sTWEAK levels > 3000 pg/mL (adjusted OR 16.43; 95% CI: 3.71–72.70), leukoaraiosis (adjusted OR 10.42; 95% CI: 2.68–39.08), and microalbuminuria (adjusted OR 1.02; 95% CI: 1.00–1.12). In our cohort, hyperthermia was independently associated with EIG after IS. The fact that microalbuminuria, leukoaraiosis, and sTWEAK were also associated with EIG suggests a relationship with increased BBB permeability.

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Cardiovascular risk of gender-affirming estrogen therapy in a transgender rat model - D. S. Escudero; V. R. Martínez; Y. Pirosanto; G. A. Colareda; M. Pis Diez; J. M. Lofeudo; O. Castillo; J. O. Vélez Rueda; E. L. Portiansky; N. G. Pérez; R. G. Díaz (Journal of Molecular Medicine, 2025)

Adaptive responses to thinning: Growth and sensitivity to hydric and thermal stress in four widely planted pine species - Àngela Manrique-Alba; Santiago Beguería; J. Julio Camarero; Antonio J. Molina; Gonzalo G. Barberá; Juan A. Blanco; Antonio M. Cachinero-Vivar; Víctor M. Castillo; Antonio D. del Campo; Álvaro Hernández; J. Bosco Imbert; María N. Jiménez; et al. (Agricultural and Forest Meteorology, 2025)

Conservation Arks: Genomic Erosion and Inbreeding in an Abundant Island Population of Koalas - Katie Gates; Jonathan Sandoval‐Castillo; Julian E. Beaman; Karen Burke da Silva; Frédérik Saltré; Katherine Belov; Carolyn J. Hogg; Corey J. A. Bradshaw; Luciano B. Beheregaray (Molecular Ecology, 2025)
The persistence of many threatened species depends on isolated habitat patches such as conservation parks, fenced reserves, and islands. While these ‘conservation arks’ provide refuge from many contemporary threats, they can also pose risks of genetic diversity loss and inbreeding depression, further exacerbating extinction risk. A pertinent example is the Kangaroo Island koala population in South Australia that originated from a few translocated founding individuals in the 1920s but now sustains a large population with a low prevalence of infectious disease. We investigated the extent and consequences of founder effects on genomic diversity, inbreeding, and adaptive potential in Kangaroo Island koalas by comparing them with mainland Australian populations using high‐coverage whole genomes. Our findings support sharp, recent declines in effective population sizes ( N e ) in both mainland and Kangaroo Island populations. However, Kangaroo Island koalas had much lower individual and population‐level diversity. Together with longer and more numerous runs of homozygosity and an increased proportion of homozygous genetic load, these results support the hypothesis that a severe bottleneck has contributed to inbreeding and maladaptation in Kangaroo Island koalas. While Kangaroo Island has the potential to conserve a viable population of koalas, we recommend genetic rescue to restore diversity and mitigate inbreeding depression in this isolated population. Our results emphasise the need for longitudinal genomic monitoring and genetic management to maintain long‐term viability and resilience in potential conservation arks. Understanding the demographic history of such populations will help inform future conservation aimed at preventing genetic erosion and preserving biodiversity.

Impacts of heat stress under oceanic climate on fertility and reproductive physiology of dairy cows subjected to hormonal synchronization - E. N. Martínez; C. Castillo; L. Avendaño-Reyes; J. Hernández; J. L. Benedito; A. Rico; P. Garcia; R. Muiño (International Journal of Biometeorology, 2025)
Regions with oceanic climates are experiencing unprecedented climatic changes. This study assesses the presence of heat stress in these regions and its impact on reproductive in Holstein cows using the Temperature-Humidity Index (THI), a measure of thermal stress. Data was collected from 159 Holstein cows across experiments. Cows underwent a modified double-ovsynch synchronization protocol, while 96 cows were inseminated based on observed estrous. Cows were examined for body temperature, follicle and uterus examination, and serum progesterone concentrations to evaluate the impact of heat stress. The results of cows pregnancy rate in double-ovsynch synchronized cows were 48.5% and 43.3% in summer and winter seasons, respectively. While the pregnancy rate in non-synchronized cows were 29.5% and 32.7% in summer and winter season, respectively. Elevated THI levels (THI ≥ 72) have adversely effects on reproductive physiology, reduced estrous expression, decreased uterine blood flow, and altered progesterone concentrations. Mild heat stress during summer months in oceanic climate negatively impacted reproductive efficiency in dairy cows, for adaptive management strategies. The double-ovsynch protocol effectively stabilized fertility across seasons, demonstrating its value in improving reproductive outcomes under varying thermal conditions.

Hydrological seasonality is a major driver of ecosystem metabolism in tropical nonwadeable rivers - María M. Castillo; Amber J. Ulseth; Aarón Jarquín‐Sánchez; Arturo Álvarez‐Merino; Krista A. Capps (Limnology and Oceanography, 2025)
Studies of annual patterns of ecosystem metabolism in rivers have primarily been conducted in temperate ecosystems, and little is known about metabolic regimes of tropical rivers. We estimated ecosystem metabolism in four nonwadeable rivers in southern México that varied in size and the extent of human disturbance. The smaller rivers with limited human disturbance showed reduced gross primary production (GPP; 1.0 and 1.7 g O 2 m −2 d −1 ), ecosystem respiration (ER; − 1.9 g O 2 m −2 d −1 ), and net ecosystem production (NEP) approaching autotrophy (− 0. 8 and − 0.3 g O 2 m −2 d −1 ) relative to rivers draining larger, more disturbed catchments (GPP, 1.2 and 2.7 g O 2 m −2 d −1 ; ER, − 5.7 and − 6.9 g O 2 m −2 d −1 ; NEP, − 3.8 and − 3.7 g O 2 m −2 d −1 ). In all rivers, GPP and ER varied seasonally with discharge. The smaller rivers exhibited a distinct pattern of greater and sustained GPP during periods of low discharge, a seasonal metabolic regime we describe as “flow decline.” In general, process–discharge relationships exhibited thresholds, with an initial decline in GPP and ER, with increasing discharge and an increase in ER at higher flows. Relative to larger and more disturbed watersheds, smaller rivers showed a more constrained metabolic fingerprint. Annual NEP (− 1033 and − 641 g C m −2 yr −1 ) in the larger rivers was more negative than the global average, supporting evidence from other studies that tropical rivers are greater contributors to CO 2 emissions than temperate ecosystems. Our study indicates that hydrological seasonality is a major driver of metabolism in tropical rivers.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Sustainable technological innovations in agriculture: Financial challenges and investment priorities under the European Green Deal - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; Francisco Jesús Gálvez-Sánchez; Francisco Camacho-Ferre (Journal of Environmental Management, 2025)

Health-related compounds and Maillard reaction products in dry and steam roasted purple carrots (Daucus carota L.) - Laura Sáez-Escudero; Gracia Patricia Blanch; Francisco J. Morales; Marta Mesías; María Luisa Ruiz del Castillo (Food Chemistry, 2025)

Climate dynamics during the last 3000 years forced environmental and sedimentation changes in southern Spain: The Laguna Grande de Archidona record - Gonzalo Jiménez-Moreno; Antonio García-Alix; Fernando Gázquez; Aurora Castillo-Baquera; Lucía Martegani; Miguel Rodríguez-Rodríguez; Marta Rodrigo-Gámiz; Francisco J. Jiménez-Espejo (CATENA, 2025)

Productivity and nutritional quality of pastures in a silvopastoral system under two harvest intervals in southeastern Mexico - Benito B. Dzib-Castillo; Fernando Casanova-Lugo; Dixan Pozo-Leyva; Ricardo L. D. Costa; Laura Macario-González; Flavia M. A. Gimenes; Luis A. Lara-Pérez; Alfonso J. Chay-Canul (Agroforestry Systems, 2025)

Different reproductive strategies influence in vitro germination in Chloraea gavilu and Chloraea crispa (Orchidaceae) - G. Pereira; D. Castillo-Novales; O. Jeldes-Cajas; J. T. Otero; C. Arriagada; C. Atala (Brazilian Journal of Botany, 2025)

Chronic arsenic exposure of ovarian surface and fallopian tube cultures induces giant and/or multinucleated cells with phagocytosis-like properties and an inflammatory phenotype - Cristina M. Andrade-Feraud; Arlet M. Acanda de la Rocha; Noah E. Berlow; Santiago Duque; Alexander Velazco; Diego Castillo; Baylee Holcomb; Ebony R. Coats; Yasmin R. Ghurani; Catherine M. Lucey; Brandon Pearson; Tomás R. Guilarte; et al. (Toxicology and Applied Pharmacology, 2025)

Unraveling spatio-temporal patterns of taxonomic, functional, and phylogenetic β-diversity of temperate ant communities after habitat simplification - G. Pérez-Toledo; M. Cuautle; C. Castillo-Guevara; J. G. Miguelena (Biodiversity and Conservation, 2025)

Parthenogenesis in the neotropical katydid Conocephalus ictus - Tzitzi M. Placier-Gallardo; Hugo J. Amaro-Lozada; Raúl Cueva del Castillo (Journal of Insect Physiology, 2025)

Age and Length at Maturity of Pelagic Thresher (Alopias pelagicus) in the Mexican Pacific - L. Daniel Carrillo-Colín; J. Fernando Márquez-Farías; J. Leonardo Castillo-Géniz; Oscar G. Zamora-García (Thalassas: An International Journal of Marine Sciences, 2025)

The tps5, tps10 and tps11 class II trehalose phosphate synthase mutants alter carbon allocation to starch and organic and amino acids at two different photoperiods in Arabidopsis - Andrea C. Ruiz-Castillo; Daniela J. Bonilla-Córdoba; Ismael Cisneros-Hernández; Norma Martínez-Gallardo; Enrique Ramírez-Chávez; John Délano-Frier (Planta, 2025)
Main conclusion Altered C and N allocation in response to short- and long photoperiods in class II TPS mutants suggest that they negatively regulate the TPS1-Tre6P metabolic regulator system in A. thaliana . Abstract The biological function of class II TPS genes remains largely enigmatic, although there is evidence that they may play an important regulatory role in plant stress responses as well as in development and growth. Recent findings indicated that part of biological function of TPSII proteins may be related to their capacity to associate with the SnRK1 regulator of metabolism in order to inhibit its nuclear activity. The results of the present study show that insertional mutants of the TPS5 , TPS10 and TPS11 class II TPS genes had a marked effect on the carbon allocation to non-structural carbohydrates, notably starch, and to organic and amino acids during both short- and long-day photoperiods. The results obtained in this study, which resembled those obtained previously in AhTPS1 overexpressing plants, suggest that these particular TPSII proteins may negatively regulate of C and N allocation to non-structural carbohydrates, organic and amino acids mediated by the TPS1-Tre6P central metabolic regulator system in A. thaliana plants. The effect observed was sometimes dependent on of the photoperiod employed and the mutant examined. The mechanism by means of which these TPS II proteins may specifically target TPSI activity and Tre6P levels in order to regulate C and N allocation in A. thaliana in response to short- and long-day photoperiods remains to be determined.

Lemongrass (Cymbopogon citratus) peroxidase-modified screen-printed graphene electrodes for electrochemical sensing of hydrogen peroxide - Ella Rodriguez; Stefania Correa; Herminsul Cano; John J. Castillo (Journal of Plant Biochemistry and Biotechnology, 2025)

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

Latitudinal propagation and solar wind drivers of Pc5 pulsations during the June 2015 geomagnetic storm - J. A. Lazzús; I. Salfate; M. N. Castillo; J. Lorca-Castillo; C. Olivares-Salazar; A. Rivera-Zepeda (Acta Geodaetica et Geophysica, 2025)

Site-specific nutrient management for rice using soil properties to adjust phosphorus and potassium supply from compound NPK fertilizer - Setia Sari Girsang; Rowena L. Castillo; Mahyuddin Syam; Zulkifli Zaini; Sunendar Kartaatmadja; Suyamto; Judith Carla Dela Torre; Irish Lorraine B. Pabuayon; Romalene A. Limpiada; Waluyo; Helmi; Samijan; et al. (Field Crops Research, 2025)

Occurrence of pharmaceuticals in muscle tissue of red drum (Sciaenops ocellatus) across subtropical estuaries: Comparison to blood plasma and implications for human exposure - W. Ryan James; Nicholas A. Castillo; Andy Distrubell; Shakira Trabelsi; Rolando O. Santos; Daniel Cerveny; Ryan J. Rezek; Ross E. Boucek; Aaron J. Adams; Jerker Fick; Tomas Brodin; Jennifer S. Rehage (Science of The Total Environment, 2025)

Development of a generalized pseudo-continuous model for fluid dynamics in packed bed reactors with a low d t / d p - Alberto Hernandez-Aguirre; Roel Hernandez-Rodriguez; J. Alberto Ochoa-Tapia; Carlos O. Castillo-Araiza (Chemical Engineering Journal, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Assessment of a base-isolated structure with semi-active low-cost viscous fluid dampers through real-time hybrid simulations - S. Vides; B. Castillo; A. Artunduaga; J. Marulanda; P. Thomson (Innovative Infrastructure Solutions, 2025)
The dynamic performance of low-rise buildings under dynamic loads presents significant challenges in structural engineering. Accurate evaluation methods are crucial for ensuring the safety and resilience of these structures, especially in seismic-prone areas. This study focuses on implementing Real-Time Hybrid Simulations (RTHS) for the assessment of structural control systems in low-rise buildings. The research integrates a numerical substructure, which models the dynamic characteristics of the building, with an experimental substructure that consists of physical devices such as base isolators, semi-active fluid viscous dampers, or hybrid control system. The RTHS method provides a sophisticated platform to evaluate the effectiveness of hybrid control systems under seismic excitations. The results demonstrated a marked improvement in predicting structural responses, with the proposed method achieving a 15.0% reduction in error compared to fixed structure. Additionally, the application of hybrid control systems showed a 25.0% increase in energy dissipation capacity compared to individual passive control. These findings contribute to the advancement of resilient design strategies, offering a quantitative framework for optimizing structural control systems in low-rise buildings.

Biome conservatism prevailed in repeated long-distance colonization of Madagascar’s mountains by Helichrysum (Compositae, Gnaphalieae) - Carme Blanco-Gavaldà; Cristina Roquet; Genís Puig-Surroca; Santiago Andrés-Sánchez; Sylvain G. Razafimandimbison; Rokiman Letsara; Nicola Bergh; Glynis V. Cron; Lucía D. Moreyra; Juan Antonio Calleja; Òscar Castillo; Randall J. Bayer; et al. (Molecular Phylogenetics and Evolution, 2025)

Leaf Gene Expression in Response to Boron Toxicity in Native Maize (Zea mays L.) Cultivars - Mirko J. Ortiz; José Delatorre-Herrera; Juan Pablo Rodriguez Calle; Gerzon Moreno; Javier Palacios; Camila Molina; Víctor Espinoza; Cristopher Low-Pfeng; José Delatorre-Castillo; Isabel Sepúlveda-Soto (Journal of Soil Science and Plant Nutrition, 2025)

Effect of pH, temperature and adsorbent mass on Cr (VI) adsorption in residues from a coal washing plant - Aime J. Garcia-Lugo; Jorge C. Ríos-Hurtado; Gloria I. Dávila-Pulido; Adrián A. González-Ibarra; Fatima P. Lara-Castillo; Sergio E. Flores-Villaseñor (Environmental Geochemistry and Health, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

Discovering Hidden Archaeal and Bacterial Lipid Producers in a Euxinic Marine System - Dina Castillo Boukhchtaber; F. A. Bastiaan von Meijenfeldt; Diana X. Sahonero Canavesi; Denise Dorhout; Nicole J. Bale; Ellen C. Hopmans; Laura Villanueva (Environmental Microbiology, 2025)
Bacterial membrane lipids are typically characterised by fatty acid bilayers linked through ester bonds, whereas those of Archaea are characterised by ether‐linked isoprenoids forming bilayers or monolayers of membrane‐spanning lipids known as isoprenoidal glycerol dialkyl glycerol tetraethers (isoGDGTs). However, this understanding has been reconsidered with the identification of branched GDGTs (brGDGTs), which are membrane‐spanning ether‐bound branched alkyl fatty acids of bacterial origin, though their producers are often unidentified. The limited availability of microbial cultures constrains the understanding of the biological sources of these membrane lipids, thus limiting their use as biomarkers. To address this issue, we identified membrane lipids in the Black Sea using high‐resolution accurate mass/mass spectrometry and inferred their potential producers by targeting lipid biosynthetic pathways encoded on the metagenome, in metagenome‐assembled genomes and unbinned scaffolds. We also identified brGDGTs and highly branched GDGTs in the suboxic and euxinic waters, potentially attributed to Planctomycetota, Cloacimonadota, Desulfobacterota, Chloroflexota, Actinobacteria and Myxococcota—based on their lipid biosynthetic genomic potential. These findings introduce new possibilities for using specific brGDGTs as biomarkers of anoxic conditions in marine environments and highlight the role of these membrane lipids in microbial adaptation.

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

Photoperiod and Light Spectrum Modulate Daily Rhythms and Expression of Genes Involved in Cell Proliferation, DNA Repair, Apoptosis and Oxidative Stress in a Seabream Embryonic Stem Cell Line - Alba Vergès-Castillo; Patricia Herrera-Pérez; Carlos Pendón; Águeda J. Martín-Robles; José A. Muñoz-Cueto (Marine Biotechnology, 2025)
The use of cell lines as alternative models for environmental physiology studies opens a new window of possibilities and is becoming an increasingly used tool in marine research to fulfil the 3R’s rule. In this study, an embryonic monoclonal stem cell line obtained from a marine teleost (gilthead seabream, Sparus aurata ) was employed to assess the effects of photoperiod (light/dark cycles vs constant dark) and light spectrum (white, blue, green, blue/green and red lights) on gene expression and rhythms of cellular markers of proliferation, DNA repair, apoptosis and cellular/oxidative stress by RT-qPCR and cosinor analyses. The results obtained revealed the optimal performance of cells under blue light (LDB), with all the genes analysed showing their highest RNA expression levels and most robust daily variations/rhythms in this condition. Under LDB, the mRNA levels of cell proliferation ( pcna ), DNA repair ( cry5 ), anti-apoptotic ( bcl2 ) and oxidative stress ( prdx2 ) markers peaked at the day-night transition, whereas pro-apoptotic ( bax ) and cell stress ( hsp70 ) markers showed their highest expression at the night-day transition, evidencing the strong synchronisation of the transcription of key genes involved in the cell cycle in this photoregime. The persistence of significant pcna , cry5 , hsp70 and prdx2 rhythms after 3 days in constant darkness reveals the endogenous and circadian nature of these rhythms. Our results highlight the importance of implementing photoperiods with light–dark cycles of blue wavelengths when performing fish cell culture research. These results reinforce and extend our previous studies, confirming the importance of lighting conditions that mimic the natural environment for the proper development of fish embryos and larvae in aquaculture.

Higher plasma levels of endocannabinoids and analogues are correlated with a worse cardiometabolic profile in middle-aged adults - Carmen Rodríguez-García; Francisco J. Osuna-Prieto; Isabelle Kohler; Joaquin Sanchez-Gomez; Samuel Ruiz-Campos; Manuel J. Castillo; Francisco J. Amaro-Gahete; Borja Martínez-Tellez; Lucas Jurado-Fasoli (Journal of Physiology and Biochemistry, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Widespread pharmaceutical exposure at concentrations of concern for a subtropical coastal fishery: Bonefish (Albula vulpes) - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Marine Pollution Bulletin, 2024)

Use of real-time ultrasound measurements of fat thickness and longissimus thoracis muscle characteristics for predicting body fat depots in crossbred hair ewes - José Carlos García-Cigarroa; Armin Abelardo Luna-Mendicuti; Jorge Rodolfo Canul-Solís; Luis Enrique Castillo-Sanchez; José Herrera-Camacho; Einar Vargas-Bello-Pérez; Alfonso J. Chay-Canul (Small Ruminant Research, 2024)

A holistic simulation model of solid-set sprinkler irrigation systems for precision irrigation - M. Morcillo; J. F. Ortega; R. Ballesteros; A. del Castillo; M. A. Moreno (Precision Agriculture, 2024)

Cadmium availability in rhizosphere and non-rhizosphere soils in cacao farms in Santander, Colombia - C. A. Adarme-Duran; J. Ágreda; P. F. B. Brandão; E. Castillo (Environmental Monitoring and Assessment, 2024)
Current research has highlighted the need to understand the factors influencing cadmium (Cd) availability in cacao-growing soils to elucidate its presence in cacao beans (the raw material for chocolate). Although literature about this topic is increasing, few report the importance of rhizosphere soils on Cd dynamics. This study aimed to understand the changes in available Cd and its association with soil properties (pH, pseudo-total Cd, available Cd (Cd-DTPA), Ca, Mg, K, Na, soil organic carbon, P, Zn, urease activity, exchangeable acidity, and cation exchange capacity) considering rhizosphere and non-rhizosphere soils. Both soil types (51 samples of each, 102 in total) were collected from two Colombian cacao farms. The medians of pseudo-total Cd (1.86 mg kg −1 ) and Cd-DTPA (0.76 mg kg −1 ) were, respectively, about threefold and fourfold higher in rhizosphere compared to non-rhizosphere soils. Principal component analysis showed a clear distinction between rhizosphere and non-rhizosphere soils based on differences in soil properties, which explained the observed changes in available Cd when comparing both soil types. Soil organic carbon and Zn were important drivers of available Cd in rhizosphere soils. Spatial distribution analysis revealed a tendency of available Cd to cluster in rhizosphere soils, and indicated hotspots within each farm. These findings highlight the importance of rhizosphere soils for Cd diagnosis and monitoring, and for improving knowledge about Cd dynamics in the soil- Theobroma cacao L. system.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Genomic Vulnerability to Climate Change of an Australian Migratory Freshwater Fish, the Golden Perch ( Macquaria ambigua ) - Emily J. Booth; Chris J. Brauer; Jonathan Sandoval‐Castillo; Katherine Harrisson; Meaghan L. Rourke; Catherine R.M. Attard; Dean M. Gilligan; Zeb Tonkin; Jason D. Thiem; Peter J. Unmack; Brenton Zampatti; Luciano B. Beheregaray (Molecular Ecology, 2024)
Genomic vulnerability is a measure of how much evolutionary change is required for a population to maintain optimal genotype‐environment associations under projected climates. Aquatic species, and in particular migratory ectotherms, are largely underrepresented in studies of genomic vulnerability. Such species might be well equipped for tracking suitable habitat and spreading diversity that could promote adaptation to future climates. We characterised range‐wide genomic diversity and genomic vulnerability in the migratory and fisheries‐important golden perch ( Macquaria ambigua ) from Australia's expansive Murray–Darling Basin (MDB). The MDB has a steep hydroclimatic gradient and is one of the world's most variable regions in terms of climate and streamflow. Golden perch are threatened by fragmentation and obstruction of waterways, alteration of flow regimes, and a progressively hotter and drying climate. We gathered a genomic dataset of 1049 individuals from 186 MDB localities. Despite high range‐wide gene flow, golden perch in the warmer, northern catchments had higher predicted vulnerability than those in the cooler, southern catchments. A new cross‐validation approach showed that these predictions were insensitive to the exclusion of individual catchments. The results raise concern for populations at warm range edges, which may already be close to their thermal limits. However, a population with functional variants beneficial for climate adaptation found in the most arid and hydrologically variable catchment was predicted to be less vulnerable. Native fish management plans, such as captive breeding and stocking, should consider spatial variation in genomic vulnerability to improve conservation outcomes under climate change, even for dispersive species with high connectivity.

Spatial distribution of dissolved free amino acids in three Iberian Atlantic estuaries - Valentina Amaral; Jesús Forja; Barbara Steger-Mähnert; Gerhard J. Herndl; Cristina Romera-Castillo (Marine Chemistry, 2024)

Correction to: Comparison of linear and nonlinear models to estimate body weight of Pelibuey ewes from body measurements - Rafael J. Macedo-Barragán; Victalina Arredondo-Ruiz; Carlos Urban Haubi-Segura; Paola Estefanía Castillo-Zamora (Tropical Animal Health and Production, 2024)

Impact of coagulation characteristics on the aggregation of microplastics in upper-ocean turbulence - F. Pizzi; M. Rahmani; C. Romera-Castillo; F. Peters; J. Grau; F. Capuano; L. Jofre (Advances in Water Resources, 2024)

Risk of prostate cancer in the proximity of industrial installations: A multicase-control study in Spain (MCC-Spain) - Javier García-Pérez; Nerea Fernández de Larrea-Baz; Virginia Lope; Alejandro Domínguez-Castillo; Ana Espinosa; Trinidad Dierssen-Sotos; Manuel Contreras-Llanes; María Ángeles Sierra; Gemma Castaño-Vinyals; Adonina Tardón; José J. Jiménez-Moleón; Ana Molina-Barceló; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

In-depth exploration of the high and normal pH beef proteome: First insights emphasizing the dynamic protein changes in Longissimus thoracis muscle from pasture-finished Nellore bulls over different postmortem times - Iliani Patinho; Daniel S. Antonelo; Eduardo F. Delgado; Laura Alessandroni; Júlio C.C. Balieiro; Carmen J. Contreras Castillo; Mohammed Gagaoua (Meat Science, 2024)

Challenges and perspectives of the circular economy in the European Union: A comparative analysis of the member states - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; Fernando Diánez-Martínez; Francisco Camacho-Ferre (Ecological Economics, 2024)

Differential tissue distribution of pharmaceuticals in a wild subtropical marine fish - N.A. Castillo; R.O. Santos; W.R. James; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; J. Fick; T. Brodin; J.S. Rehage (Aquatic Toxicology, 2024)

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

A functional light-entrainable molecular clock is revealed in gilthead seabream (Sparus aurata) from early developmental stages using an embryonic stem cell line - Alba Vergès-Castillo; José A. Muñoz-Cueto; Javier Durán-Sáez; Carlos Pendon; Águeda J. Martín-Robles (Aquaculture, 2024)

P26-01 Hexagonal boron nitride (hBN) and hBN-reinforced thermoplastic polyurethane composite: an in vitro hazard characterization using human skin and lung cells - M. Carlin; J. Kaur; D.Z. Ciobanu; Z. Song; M. Olsson; T. Totu; G. Gupta; G. Peng; V. Jehová González; I.J. Janica; V. Fuster Pozo; S. Chortarea; et al. (Toxicology Letters, 2024)

P18-09 Quantitative analysis of micro and nanoplastics in biological tissues: implications for environmental and human health - M. Garcia; A. Nihart; R. Liu; E. El Hayek; E. Castillo; B. Bleske; E. Barrozo; M.A. Suter; J. Scott; K. Forsythe; N. Adolfi; D. Gallego Umana; et al. (Toxicology Letters, 2024)

Sustainable urban noise monitoring network with renewable bioenergy sources: An energy cost–benefit analysis - Alejandro Castillo-Atoche; Naemi Maile; Johan J. Estrada-Lopez; Edith Osorio-de-la-Rosa; Orlando Palma-Marrufo; Javier Vázquez-Castillo (Sustainable Cities and Society, 2024)

Adsorption of amine surfactants onto kaolinite: A multiscale investigation - J. Lainé; Y. Foucaud; J.W. Hounfodji; P. Pelée de Saint-Maurice; A. Bonilla-Petriciolet; D.I. Mendoza-Castillo; H. Turrer; M. Badawi (Minerals Engineering, 2024)

Diversity and structure of prokaryotic assemblages in a thermally stratified tropical lake - Jesús Torres-Huesca; Jazmín Santillán; Yislem Beltrán; Rafael A. López-Martínez; Miroslav Macek; Luisa I. Falcón; Martín Merino-Ibarra; Patricia M. Valdespino-Castillo; Jesús T. Martínez-Díaz; Javier Alcocer; Rocío J. Alcántara-Hernández (Limnologica, 2024)

Identifying pathways of pharmaceutical exposure in a mesoconsumer marine fish - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; S. Trabelsi; A. Distrubell; M. Sandquist; J. Fick; T. Brodin; et al. (Journal of Hazardous Materials, 2024)

Genetic and phenotypic differentiation in functional traits of Iris pseudacorus L. in native and introduced Mediterranean climate ranges - B. Gallego-Tévar; B. J. Grewell; J. F. Gaskin; J. M. Castillo (Biological Invasions, 2024)
Intraspecific variation in functional traits between native and introduced plant species may underlie resilience and invasiveness of introduced species. We explored if observed phenotypic variation of Iris pseudacorus L. between populations in the native vs. introduced ranges results from genetic differentiation and/or phenotypic plasticity. Seeds were collected from populations along estuarine stress gradients within populations in both Guadalquivir Estuary (Andalusia, Spain) and San Francisco Bay-Delta Estuary (California, USA). Genetic analysis was performed on leaf tissue from plants in each seed donor population. Germinants (n = 48: 6 plants × 4 populations × 2 ranges) were grown for 12 months in a common garden experiment (CGE). We then evaluated 25 traits including growth, biomass allocation, morphological and biochemical responses. Geographic range explained relative intraspecific trait variation segregating native from introduced phenotypes. Native plants had lower specific leaf area (− 34%) and carbohydrate concentrations in rhizomes (− 63%) than introduced plants, providing evidence of genetic differentiation. Higher genetic diversity and 27% higher phenotypic variation (CGE) of native vs. introduced plants indicated longer-term adaptive processes in the native range. Genetic distance of introduced populations (field) increased along with their phenotypic distance (CGE), suggesting rapid genetic differentiation. Phenotypic plasticity also explained some observed inter-range differences under field conditions not expressed by plants in the CGE. Management of the introduced I. pseudacorus populations should be established urgently since they represent novel genotypes with key functional traits that can support invasiveness through increased competitive ability and physiological stress tolerances to sea level rise.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Exploring proteasome inhibition using atomic weighted vector indices and machine learning approaches - Yoan Martínez-López; Juan A. Castillo-Garit; Gerardo M. Casanola-Martin; Bakhtiyor Rasulev; Ansel Y. Rodríguez-Gonzalez; Oscar Martínez-Santiago; Stephen J. Barigye (Molecular Diversity, 2024)

Acceptability and Feasibility of Survivorship Group Medical Visits for Breast Cancer Survivors in a Safety Net Hospital - Evelin Trejo; Ana I. Velazquez; Elizabeth Castillo; Paul Couey; Barbara Cicerelli; Robin McBride; Nancy J. Burke; Niharika Dixit (Journal of Cancer Education, 2024)
Providing cost-effective, comprehensive survivorship care remains a significant challenge. Breast cancer survivors (BCS) who have limited income and are from marginalized racial and ethnic groups experience a worse quality of life and report higher distress. Thus, innovative care models are required to address the needs of BCS in low resource settings. Group medical visits (GMV), utilized in chronic disease management, are an excellent model for education and building skills. This single-arm intervention study was conducted at a public hospital in California. GMVs consisted of five 2-h weekly sessions focused on survivorship care planning, side effects of treatment and prevention, emotional health, sexual health, physical activity, and diet. The patient navigators recruited three consecutive GMV groups of six English-speaking BCS ( N = 17). A multidisciplinary team delivered GMVs, and a patient navigator facilitated all the sessions. We used attendance rates, pre- and post-surveys, and debriefing interviews to assess the feasibility and acceptability of the intervention. We enrolled 18 BCS. One participant dropped out before the intervention started, 17 BCS consistently attended and actively participated in the GMV, and 76% (13) attended all planned sessions. Participants rated GMVs in the post-survey and shared their support for GMVs in debriefing interviews. The BCS who completed the post-survey reported that GMVs increased their awareness, confidence, and knowledge of survivorship care. GMVs were explicitly designed to address unmet needs for services necessary for survivorship care but not readily available in safety net settings. Our pilot data suggest that patient-navigator-facilitated GMVs are a feasible and acceptable model for integrating survivorship care in public hospitals.

Structure and carbon stocks of accessible mangroves under different conservation status in the Colombian Caribbean - K. Anggi Hapsari; Wilder José Borrero Avellaneda; Barend van Maanen; Juan C. Restrepo; Jaime Polanía; Deysser Jose Sibaja Castillo; Luisa Fernanda Gómez Vargas; J. Alexandra Rodríguez-Rodríguez; Dunia H. Urrego (Forest Ecology and Management, 2024)

Influence of human emotions on conservation attitudes toward relevant wildlife species in El Triunfo Biosphere Reserve, Mexico - Nathalia M. Castillo-Huitrón; Eduardo J. Naranjo; Dídac Santos-Fita; Mateo Peñaherrera-Aguirre; Pavol Prokop; Rodrigo Cisneros; Silvia Vaca Gallegos; Zuzana Ježová (Biodiversity and Conservation, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Terrestrial and Martian space weather: A complex systems approach - Abraham Chian; Rodrigo Miranda; Cesar Bertucci; Xóchitl Blanco-Cano; Joe Borovsky; Sergio Dasso; Ezequiel Echer; Adriane Franco; Kirolosse M. Girgis; J. Américo González-Esparza; Tohru Hada; Hiroshi Hasegawa; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

Strategic analysis of the sustainability of the Andalusian primary sector. An instrument for resilient management - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; Valentín Molina-Moreno; Francisco Camacho-Ferre (Journal of Cleaner Production, 2024)

Exercise-induced changes in plasma S-Klotho levels are associated with the obtained enhancements of heart rate variability in sedentary middle-aged adults: the FIT-AGEING study - Ginés Navarro-Lomas; Abel Plaza-Florido; Alejandro De-la-O; Manuel J. Castillo; Francisco J. Amaro-Gahete (Journal of Physiology and Biochemistry, 2024)

Perception of photovoltaic energy consumption in the Spanish primary sector. An environmentally profitable alternative - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; Emilio Abad-Segura; Francisco Camacho-Ferre (Journal of Environmental Management, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Optimization of cost-effective enzymatic saccharification using low-cost protic ionic liquid as pretreatment agent in Agave bagasse - Jose A. Pérez-Pimienta; Damián J. Castillo-Preciado; Víctor González-Álvarez; Hugo O. Méndez-Acosta (Waste Management, 2024)

Role of indigenous microbial communities in the mobilization of potentially toxic elements and rare-earth elements from alkaline mine waste - S. Cebekhulu; A. Gómez-Arias; A. Matu; J. Alom; A. Valverde; M.A. Caraballo; O. Ololade; P. Schneider; J. Castillo (Journal of Hazardous Materials, 2024)

The importance of assets for coping with COVID-19 and other shocks - Julio A. Berdegué; María J. Castillo; Ileana Gómez; Gustavo Gordillo; José Navea; Irvin Rojas; Rodrigo Yáñez (Global Food Security, 2024)

Giving gully detection a HAND – Testing the scalability and transferability of a semi-automated object-orientated approach to map permanent gullies - George Olivier; Marco J. Van De Wiel; Carlos Castillo; Miguel Vallejo Orti; Willem P. de Clercq (CATENA, 2024)

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Assessing the impact of land use change on different components of plant diversity in a tropical montane cloud forest of Mexico - Gonzalo Castillo-Campos; José G. García-Franco; M. Luisa Martínez; Gabriela Vázquez; Jesús J. Pale-Pale; Mirna R. Zamudio Pérez; Octavio Pérez-Maqueo (Biodiversity and Conservation, 2024)

Understanding pharmaceutical exposure and the potential for effects in marine biota: A survey of bonefish (Albula vulpes) across the Caribbean Basin - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; T. Goldberg; L. Campbell; A.U. Perez; J.J. Schmitter-Soto; J.P. Lewis; et al. (Chemosphere, 2024)

Gravimetric survey and modelling of a tectonic indenter boundary: The Palomares Fault Zone (Betic Cordillera, Iberia) - V. Tendero-Salmerón; G. Ercilla; L. González-Castillo; A. Madarieta-Txurruka; F.J. Martínez-Moreno; F. Estrada; J. Galindo-Zaldivar (Tectonophysics, 2024)

Effectiveness of dietary heat-killed Bacillus subtilis harboring plasmid containing 60 copies of CpG-ODN 1668 against Vibrio harveyi in Penaeus vannamei - Wahyu Purbiantoro; Vinh Huynh-Phuoc; B. R. J. Castillo-Corea; Omkar Vijay Byadgi; Ta-Chih Cheng (Veterinary Research Communications, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Efficacy of a mirid predator and an eulophid parasitoid to the tomato potato psyllid Bactericera cockerelli control on pepper plants - Alejandro O. Guzmán-Pedraza; Ana Mabel Martínez; Ángel Rebollar-Alviter; Luis J. Palma-Castillo; Sinue I. Morales-Alonso; Juan M. Chavarrieta-Yáñez; José I. Figueroa; Samuel Pineda (BioControl, 2024)

Hg and Se in Muscle and Liver of Blue Shark (Prionace glauca) from the Entrance of the Gulf of California: An Insight to the Potential Risk to Human Health - M. E. Rechimont; J. Ruelas-Inzunza; F. Amezcua; F. Paéz-Osuna; J. L. Castillo-Géniz (Archives of Environmental Contamination and Toxicology, 2024)

Predictive models for grape downy mildew (Plasmopara viticola) as a decision support system in Mediterranean conditions - M. Puelles; J. Arbizu-Milagro; F.J. Castillo-Ruiz; J.M. Peña (Crop Protection, 2024)

Detection of subsurface bruises in plums using spectral imaging and deep learning with wavelength selection - S. Castillo-Girones; R. Van Belleghem; N. Wouters; S. Munera; J. Blasco; W. Saeys (Postharvest Biology and Technology, 2024)

Recent summer warming over the western Mediterranean region is unprecedented since medieval times - Ulf Büntgen; Frederick Reinig; Anne Verstege; Alma Piermattei; Marcel Kunz; Paul Krusic; Philip Slavin; Petr Štěpánek; Max Torbenson; Edurne Martinez del Castillo; Tito Arosio; Alexander Kirdyanov; et al. (Global and Planetary Change, 2024)

Assessment of beef sensory attributes and physicochemical characteristics: A comparative study of intermediate versus normal ultimate pH striploin cuts - Iliani Patinho; Cecylyana Leite Cavalcante; Erick Saldaña; Mohammed Gagaoua; Jorge H. Behrens; Carmen J. Contreras-Castillo (Food Research International, 2024)

Simultaneous adsorption of amoxicillin and ciprofloxacin on agricultural soils and by-products used as bio-adsorbents: Unraveling the interactions in complex systems - Raquel Cela-Dablanca; Ainoa Míguez-González; Ana Barreiro; Lucia Rodríguez-López; Manuel Arias-Estévez; Avelino Núñez-Delgado; María J. Fernández-Sanjurjo; Ventura Castillo-Ramos; Esperanza Álvarez-Rodríguez (Environmental Research, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Integrating 4-D light-sheet fluorescence microscopy and genetic zebrafish system to investigate ambient pollutants-mediated toxicity - Sheila Gonzalez-Ramos; Jing Wang; Jae Min Cho; Enbo Zhu; Seul-Ki Park; Julie G. In; Srinivasa T. Reddy; Eliseo F. Castillo; Matthew J. Campen; Tzung K. Hsiai (Science of The Total Environment, 2023)

Leaching tests reveal fast aluminum fluoride release from ashfall accumulated in La Palma (Canary Islands, Spain) after the 2021 Tajogaite eruption - J. Sánchez-España; M. Pilar Mata; J. Vegas; G. Lozano; J. Mediato; J. Martínez Martínez; I. Galindo; N. Sánchez; B. del Moral; B. Ordóñez; A. de Vergara; A. Nieto; et al. (Journal of Volcanology and Geothermal Research, 2023)

Assessing earlywood-latewood proportion influence on tree-ring stable isotopes - M.C.A. Torbenson; U. Büntgen; P. Römer; O. Urban; M. Trnka; A. Ač; F. Reinig; M. Rybníček; T. Kolář; T. Arosio; E. Martinez del Castillo; E. Koňasová; et al. (Dendrochronologia, 2023)

Petrogenesis of alkaline magmas across a continent to ocean transect, northern Ross Sea, Antarctica - K. Durkin; J.M.D. Day; K.S. Panter; J.-F. Xu; P.R. Castillo (Chemical Geology, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Assessment of photo electro-Fenton and solar photo electro-Fenton processes for the efficient degradation of asulam herbicide - Héctor H. Vigil-Castillo; Edgar J. Ruiz-Ruiz; Khirbet López-Velázquez; Laura Hinojosa-Reyes; Octavio Gaspar-Ramírez; Jorge L. Guzmán-Mar (Chemosphere, 2023)

Application of an Fe-TAML/H2O2 system for rapid degradation of organic matter - Patricio J. Espinoza-Montero; Carolina Burneo; Amanda Cevallos; G. Xavier Castillo-Cabrera; Sofía Peñafiel-Vicuña; Carlos Martínez-Huitle; Lenys Fernández; José R. Mora (Journal of Environmental Chemical Engineering, 2023)

Ecological aspects of false killer whales ( Pseudorca crassidens ) from Mexican Pacific and Southern California waters - Camila Lazcano‐Pacheco; Acilegna J. Castillo‐Sánchez; Christian D. Ortega‐Ortiz; Ibiza Martínez‐Serrano; Francisco Villegas‐Zurita; Astrid Frisch‐Jordán; Oscar R. Guzón‐Zatarain; Katherina Audley; Nicola Ransome; Jaime Bolaños‐Jiménez; Jorge Urbán‐R.; Annie B. Douglas (Marine Mammal Science, 2023)

Assessment of the sustainability of the European agri-food sector in the context of the circular economy - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; María J. López-Serrano; Francisco Camacho-Ferre (Sustainable Production and Consumption, 2023)

Adsorption of antibiotics on bio-adsorbents derived from the forestry and agro-food industries - Ainoa Míguez-González; Raquel Cela-Dablanca; Ana Barreiro; Lucia Rodríguez-López; Andrés Rodríguez-Seijo; Manuel Arias-Estévez; Avelino Núñez-Delgado; María J. Fernández-Sanjurjo; Ventura Castillo-Ramos; Esperanza Álvarez-Rodríguez (Environmental Research, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Screening of medicinal plants from El Salvador for anti-viral activity against Herpes simplex 1 - José Franco-Espínola; Marvin J. Núñez; Y. Mabel Sanabria-Ramírez; Carlos Fabio Villar-Duarte; Ulises G. Castillo; Guadalupe Cantero-González; Marcos Florentín-Pavía; Patricia Langjahr; Pablo Hernán Sotelo Torres (Natural Product Research, 2023)

Binary fluoride and As(V) adsorption in water using pleco fish bone chars - Sergio A. Cruz-Briano; Nahum A. Medellin-Castillo; Pablo Delgado-Sanchez; Guillermo J. Castro-Larragoitia; Roberto Leyva-Ramos; Miguel A. Cortina-Rangel; Gladis J. Labrada-Delgado; Diana E. Villela-Martinez; Alfredo I. Flores-Rojas; Lázaro A. Gonzalez-Fernandez; Hilda G. Cisneros-Ontiveros (Environmental Science and Pollution Research, 2023)

An integrated analysis of the Mexican electrical system’s metabolic pattern and industry sector in the energy transition - Miguel A. Morales Mora; Andrea Marín Rovira; Vicente A. Soriano Ramirez; Patricia López Rivera; Omar Guillen Solis; Vincent Pozos Castillo; Gonzalo AngelesOrdoñez; Alejandro Castillo Antonio; Francisco J. Sánchez Ruíz (Environment, Development and Sustainability, 2023)

Bacterial communities shift and influence in an acid mine drainage treatment using barium carbonate disperse alkaline substrate system - J. Castillo; J. Alom; A. Gomez-Arias; S. Cebekhulu; A. Matu; E. Cason; A. Valverde (Science of The Total Environment, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Volatile organic compounds measured by proton transfer reaction mass spectrometry over the complex terrain of Quintero Bay, Central Chile - Rodrigo J. Seguel; René Garreaud; Ricardo Muñoz; Deniz Bozkurt; Laura Gallardo; Charlie Opazo; Héctor Jorquera; Lucas Castillo; Camilo Menares (Environmental Pollution, 2023)

Alley cropping agroforestry systems change weed community composition and reduce dominant weed species associated with corn in southern Mexico - Fernando Casanova-Lugo; Luis A. Lara-Pérez; Benito Dzib-Castillo; Jesús A. Caamal-Maldonado; Pablo J. Ramírez-Barajas; William R. Cetzal-Ix; Héctor Estrada-Medina (Agriculture, Ecosystems & Environment, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Prioritization of areas for groundwater monitoring using analytic hierarchy process method in Geographic Information Systems: a case of Mexico - J. M. Esquivel-Martínez; J. L. Expósito-Castillo; M. V. Esteller-Alberich; M. A. Gómez-Albores; C. M. Medina-Rivas; C. R. Fonseca-Ortiz (International Journal of Environmental Science and Technology, 2023)

Composites of Co-Al hydrotalcites and carbon nanomaterials for photocatalytic H2 production - Dolores G. Gil-Gavilán; Daniel Cosano; Miguel Castillo-Rodríguez; Gustavo de Miguel; Dolores Esquivel; César Jiménez-Sanchidrián; José R. Ruiz; Francisco J. Romero-Salguero (Applied Clay Science, 2023)

Re‐estimation of juvenile Isurus oxyrinchus growth in the Mexican Pacific through a multimodel inference approach and verification of growth band periodicity - José Alberto Rodríguez‐Madrigal; Javier Tovar‐Ávila; José Leonardo Castillo‐Geniz; Carlos Javier Godínez‐Padilla; J Fernando Márquez‐Farías; David Corro‐Espinosa (Journal of Fish Biology, 2023)
An update of the age and growth for juveniles of the short fin mako shark ( I. oxyrinchus ) from the Mexican Pacific is presented, based on the analysis of growth band counts from dorsal vertebrae of 198 individuals [110 females, 74–231 cm of total length (TL) and 88 males, 72–231 cm TL) caught during 2008–2018. New available information on vertebral growth band periodicity (biannual deposition in juveniles) and the convenience of using vertebrae form the dorsal region over the cervical region to count growth bands, as well as a multimodel approach, were used. The von Bertalanffy (VB) growth model, Gompertz, logistic and two parameters of VB (2‐VB) were fitted to the length‐at‐age. Only ages ≤6 years were used for the fitting of the models and their performance was compared with the small‐sample bias‐corrected form of the Akaike information criterion ( AIC c), their differences ( and weights (). Following a multimodel inference approach, the model averaged asymptotic length (), length‐at‐age 0 () and their unconditional standard error (), were estimated for each sex scenario using the three‐parameter version of each model. The precision of growth band counts was acceptable for the different methods used and by two different readers. The centrum edge analysis (CEA) and marginal increment analysis (MIA) did not support the hypothesis of biannual band pair formation for juveniles, likewise for adults the periodicity could not be verified due to the small sample of large animals. Age was estimated assuming the formation of two pairs of growth bands per year during the first 5 years and one pair of bands per year afterwards considering direct validation information. The estimated ages in years ranged from 0–14 for females and 0–6 for males. The Kimura likelihood ratio test showed no differences in the growth curves of juveniles by sex ( P > 0.05). According to the AIC c, the 2‐VB model better fitted the length‐at‐age data for combined sexes ( L inf = 386.4 cm, k = 0.12 years −1 , L 0 = 70 cm). The model averaged and were 378.3 cm () and 69.5 cm (), respectively. The growth parameters determined for juveniles of I. oxyrinchus are similar to those estimated in other regions, showing relatively fast growth rate as previously reported, medium longevity in comparison to other shark species and natural mortality close to that reported in the last stock assessment for the North Pacific Ocean. These life‐history parameters should be considered to evaluate the population in the region and to develop better fishery management and conservation measures.

Human-induced metals accumulation in sediments of an industrialized bay of northern Chile. An enrichment and ecological risk assessment based on preindustrial values - J. Valdés; Luc Ortlieb; A. Sifeddine; A. Castillo (Marine Pollution Bulletin, 2023)

Cross-sectional associations of persistent organic pollutants measured in adipose tissue and metabolic syndrome in clinically diagnosed middle-aged adults - Iris Reina-Pérez; Francisco Artacho-Cordón; Vicente Mustieles; Daniel Castellano-Castillo; Fernando Cardona; Inmaculada Jiménez-Díaz; Jose A. López-Medina; Juan Alcaide; Luis Ocaña-Wilhelmi; Luz M. Iribarne-Durán; Juan P. Arrebola; Nicolás Olea; et al. (Environmental Research, 2023)

Novel polypropylene-TiO2:Bi spherical floater for the efficient photocatalytic degradation of the recalcitrant 2,4,6-TCP herbicide - P.C. Hernández-Del Castillo; J. Oliva; B.P. Núñez-Luna; V. Rodríguez-González (Journal of Environmental Management, 2023)

Surface wind strength and sea surface temperature connections along the south peruvian coast during the last 150 years - F. Briceño-Zuluaga; V. Flores-Aqueveque; J. Nogueira; A. Castillo; J. Cardich; J. Rutllant; S. Caquineau; A. Sifeddine; R. Salvatteci; J. Valdes; D. Gutierrez (Aeolian Research, 2023)

Synergistic electrocoagulation–precipitation process using magnesium electrodes for denim wastewater treatment: Bifunctional support electrolyte effect - Juan Marcelo Zaldivar-Díaz; Verónica Martínez-Miranda; Luis Antonio Castillo-Suárez; Ivonne Linares-Hernández; Marcos J. Solache Ríos; Ana Elisa Alcántara-Valladolid (Journal of Water Process Engineering, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Methodology for the fast direct estimation of spectral radiative transport properties in microalgae photobioreactors - Luis Angel Castillo; Patricio J. Valadés-Pelayo; Hugo J. Avila-Paredes; Juan J. Cabello; Argelia Balbuena (Chemical Engineering Journal, 2023)

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Bone appétit: DNA metabarcoding as a non-lethal alternative to morphological dietary assessment in Atlantic bonefish (Albula vulpes) - Lewis J. Campbell; Nicholas A. Castillo; Jonathan Shenker; Leah A. Owens; Rolando O. Santos; Aaron J. Adams; Jennifer S. Rehage; Kate E. Denton; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Using recreational tournament records to construct a 53-year time series of the Florida Keys recreational Bonefish fishery - Ross E. Boucek; Jennifer S. Rehage; Nicholas A. Castillo; Elijah Dwoskin; Steven M. Lombardo; Rolando Santos; Carl Navarre; Michael Larkin; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Ensuring equitable access to ocean and coastal information to advance knowledge and inform decision-making: The global Aquatic Sciences and Fisheries Abstracts - Diana J. Castillo; Tamsin Vicary; Maria Kalentsits; Suzuette S. Soomai; Bertrum H. MacDonald (Ocean & Coastal Management, 2023)

Exposure to secondhand aerosol from electronic cigarettes at homes: A real-life study in four European countries - Beladenta Amalia; Marcela Fu; Olena Tigova; Montse Ballbè; Blanca Paniello-Castillo; Yolanda Castellano; Vergina K. Vyzikidou; Rachel O'Donnell; Ruaraidh Dobson; Alessandra Lugo; Chiara Veronese; Raúl Pérez-Ortuño; et al. (Science of The Total Environment, 2023)

Petrology, metallogeny and U-Pb geochronology of the paleoproterozoic mafic-ultramafic Hamutenha intrusion, Angolan Shield - Marc Campeny; Joaquín A. Proenza; Montgarri Castillo-Oliver; Lisard Torró; Cristina Villanova-de-Benavent; Joan Carles Melgarejo; Antonio O. Gonçalves; Manuel J. Román-Alpiste; Idael F. Blanco-Quintero; Xavier Llovet; Júlia Farré-de-Pablo (Journal of African Earth Sciences, 2023)

Hydrogeochemical and isotopic signatures elucidate deep subsurface hypersaline brine formation through radiolysis driven water-rock interaction - D.M. Nisson; T.L. Kieft; H. Drake; O. Warr; B. Sherwood Lollar; H. Ogasawara; S.M. Perl; B.M. Friefeld; J. Castillo; M.J. Whitehouse; E. Kooijman; T.C. Onstott (Geochimica et Cosmochimica Acta, 2023)

Palaeozoic – Early Mesozoic geological history of the Antarctic Peninsula and correlations with Patagonia: Kinematic reconstructions of the proto-Pacific margin of Gondwana - Teal R. Riley; Alex Burton-Johnson; Michael J. Flowerdew; Fernando Poblete; Paula Castillo; Francisco Hervé; Philip T. Leat; Ian L. Millar; Joaquin Bastias; Martin J. Whitehouse (Earth-Science Reviews, 2023)

Seed Viability, Spikelet Dispersal, Seed Banks and Seed Storage Requirements for Native and Invasive Cordgrasses (Genus Spartina) in Southwest Iberian Peninsula - M. Dolores Infante-Izquierdo; Ruth Romero-Martín; Jesús M. Castillo; Brenda J. Grewell; Jesús J. Soriano; F. Javier J. Nieva; Adolfo F. Muñoz-Rodríguez (Wetlands, 2023)
Seed banks play an important role in determining the spatial and temporal distribution of halophytes in salt marshes. We tested the ability of native Spartina maritima and invasive S. densiflora spikelets to disperse by flotation on water with different salinity concentrations, and the longevity of spikelet viability relative to environmental conditions including dry or wet storage at low or moderate temperatures, and aqueous salinity concentrations from fresh to sea water. We quantified pre-dispersal seed production and pre- and post-dispersal focal Spartina spp. presence in seed banks along intertidal gradients within salt marshes at the Gulf of Cádiz (Southwest Iberian Peninsula). Spartina densiflora spikelets, especially from middle and high elevation marshes, showed greater ability than S. maritima to remain afloat, which suggests this species could be dispersed over longer distances. Wet-stored Spartina seeds were able to maintain viability for months, while seeds under dry storage rapidly lost viability. This decline was most significant for S. maritima , and for seeds stored at moderate temperatures. Storage of spikelets under wet and cold conditions optimized spikelet viability. Native S. maritima did not establish transient or persistent seed banks, while invasive S. densiflora established transient seed banks mainly at higher marsh elevations. Our results on the dynamics of seed dispersal and seed banks and seedling recruitment provide fundamental knowledge that can be applied for conservation of native S. maritima , management of invasive S. densiflor a, and ecological restoration of tidal salt marshes.

Nitrogen and phosphorus budget in an intensive irrigation area and effects on littoral water and groundwater (Yaqui Valley, Northwestern Mexico) - B. R. Almazán; M. V. Esteller; S. E. Garrido-Hoyos; J. L. Expósito-Castillo; C. Díaz-Delgado; J. C. García-Colín (Environmental Monitoring and Assessment, 2023)

Structure and activity of microbial communities in response to environmental, operational, and design factors in constructed wetlands - M. Verduzo Garibay; A. Fernández del Castillo; J. de Anda; C. Senés-Guerrero; M. S. Gradilla-Hernández (International Journal of Environmental Science and Technology, 2022)

Molecular insights into the invasion dynamics of Carcinus crabs in South Africa - Clova A. Mabin; Tamara B. Robinson; John R. U. Wilson; Heidi Hirsch; Maria L. Castillo; Michelle Jooste; Johannes J. Le Roux (Biological Invasions, 2022)
Knowledge of the introduction history and spread dynamics of invasive species can provide important insights for management (Ens et al. in Environ Rev (in press), 2022), however such information is often unavailable for accidental introductions. Here we infer how the European shore crab, Carcinus maenas , and its congener, the Mediterranean shore crab, C. aestuarii , were introduced to and spread within South Africa. We do this using nuclear microsatellite data and Bayesian assignment tests and Approximate Bayesian Computation (ABC) modelling that included samples from the native and other invasive ranges of these two species. We also compared the genetic diversity and structure of one of the South African populations during and after intensive management, with that of another, unmanaged, population. South African populations had higher genetic diversity than invasive Carcinus populations from elsewhere in the world. Moreover, the ABC analyses suggest that South African populations originated from an admixture event between individuals of C. maenas from a population in the native range and an invasive population from Canada. We also identified instances of hybridisation between Carcinus maenas and C. aestuarii in South Africa. South African populations showed no genetic structure, suggesting either extensive migration between them or that populations arose from the same initial introduction. Management of Carcinus did not affect genetic diversity or structure, and we suspect that the management duration was insufficient to target a full generation of crabs. Together these results suggest multiple introductions and/or high propagule pressure to South Africa, crab (larval or adult) movement between existing populations, and some hybridisation. For eradication from South Africa to be achieved, management would need to concurrently target all known invasive populations and clearly establish that new introductions could be prevented.

Mosquito control opportunities amid regulations within the tidal marshes of the San Francisco Bay Area - Erika B. Castillo; Ryan J. Clausnitzer; Eric J. Haas-Stapleton (Wetlands Ecology and Management, 2022)

Title: Present status and management of coastal lagoons in the Sabana–Camagüey Archipelago I: environmental baseline at lagoons of Cayo Sabinal - R. González-De; Zayas; M. Merino-Ibarra; J. A. Lestayo González; F. S Castillo – Sandoval (Thalassas: An International Journal of Marine Sciences, 2022)

Identification of Microcrustaceans as Potential Bioindicators of Arsenic in Tropical Water Bodies - Yadira J. Mendoza-Chávez; José L. Uc-Castillo; Martha A. Gutiérrez-Aguirre; Adrián Cervantes-Martínez; Nadia Martínez-Villegas (Archives of Environmental Contamination and Toxicology, 2022)

Metaomics unveils the contribution of Alteromonas bacteria to carbon cycling in marine oxygen minimum zones - Carlos Henríquez-Castillo; Alvaro M. Plominsky; Salvador Ramírez-Flandes; Anthony D. Bertagnolli; Frank J. Stewart; Osvaldo Ulloa (Frontiers in Marine Science, 2022)
Gammaproteobacteria of the genus Alteromonas are prominent members of pelagic marine microbial communities, playing critical roles in the aerobic degradation of particulate organic matter. Comparative genomic studies of these microorganisms have mainly focused on the metabolic and genomic plasticity of strains isolated primarily from oxygenated environments. In this study, we show that Alteromonas significantly contribute to marine microbial communities from suboxic waters ([O 2 ] < 5 uM) in both the free-living (FL) and particle-attached (PA) fractions, but considerably decrease in abundance in the anoxic waters. The highest proportion of Alteromonas transcripts was found within the secondary fluorescence maximum (SFM) of Oxygen Minimum Zones (OMZs). This metatranscriptomic information suggests an in situ coupling of Alteromonas iron (Fe) and carbon metabolisms, and a relevant role of the glyoxylate cycle across the different layers of the OMZs. This study demonstrates that Alteromonas is an abundant and active member of the OMZ microbial communities, with a potentially significant impact on the carbon cycling in these ecosystems. These results provide valuable environmental evidence to support previous culture-based studies assessing the physiology and ecology of these ubiquitous marine heterotrophs under low-oxygen conditions.

Cytotoxic and antiproliferative activity of thiazole derivatives of Ochraceolide A - Angel D. Herrera-España; Jenner Us-Martín; Carlos Quintal-Novelo; Gumersindo Mirón-López; Ramiro F. Quijano-Quiñones; David Cáceres-Castillo; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Natural Product Research, 2022)

Aridification‐driven evolution of a migratory fish revealed by niche modelling and coalescence simulations - Emily J. Booth; Jonathan Sandoval‐Castillo; Catherine R. M. Attard; Dean M. Gilligan; Peter J. Unmack; Luciano B. Beheregaray (Journal of Biogeography, 2022)
Aim Major knowledge gaps exist regarding the evolution of arid zone organisms. For freshwater species with high dispersal potential, little is known if historical aridification influenced connectivity across drainage divides and impacted on their divergence and diversification. We tested the hypothesis that the historical aridification of Australia promoted the isolation and influenced the demographic histories and evolutionary divergence of a migratory group of freshwater obligates. Location Central and eastern Australia; Murray–Darling Basin (MDB), Lake Eyre Basin (LEB), Fitzroy Basin (FIT). Taxon Three lineages of golden perch ( Macquaria ambigua ), a widespread fishery resource from inland Australia. Methods We obtained genome‐wide data for golden perch sampled throughout their range. Phylogenetic relationships were reconstructed using maximum likelihood. Species distribution modelling was used to predict contemporary and past distributions for the three lineages and to develop hypotheses regarding their biogeographic and demographic histories. Hypotheses were independently tested using coalescent simulations in fastsimcoal and DIYABC with the genomic dataset. Results We found evidence for three reciprocally monophyletic lineages that have experienced little to nil genetic connectivity since divergence. Coalescent models suggest that the coastal (FIT) and inland (MDB and LEB) lineages diverged ~103 thousand years ago (ka), followed by the split of MDB and LEB lineages ~58 ka. These timings agree with reductions of large freshwater environments in Australia during the late Pleistocene. Species distribution models show an extreme decrease in habitat during the Last Glacial Maximum ~21 ka, consistent with inferred demographic contractions in coalescent tests. Main conclusions We reveal that aridification of Australia during the late Pleistocene has driven and reinforced the divergence of a migratory freshwater obligate. Our findings are important for informing the conservation management of aquatic organisms under climate change. This work further demonstrates the value of using species distribution modelling to formulate diversification hypotheses and to improve interpretation of coalescent analyses.

Different exercise training modalities similarly improve heart rate variability in sedentary middle-aged adults: the FIT-AGEING randomized controlled trial - Ginés Navarro-Lomas; Manuel Dote-Montero; Juan M. A. Alcantara; Abel Plaza-Florido; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2022)
Purpose This study aimed to investigate the influence of different exercise training modalities on heart rate variability (HRV) in sedentary middle-aged adults; and to study whether changes in health-related outcomes (i.e., body composition and cardiometabolic risk) are associated with those hypothetical HRV changes in sedentary middle-aged adults. Methods A total of 66 middle-aged adults (53.6 ± 4.4 years old; 50% women) were enrolled in the FIT-AGEING study. We conducted a 12-week randomized controlled trial. The participants were randomly assigned to 4 groups: (a) a control group (no exercise); (b) a physical activity recommendation from the World Health Organization group (PAR); (c) a high-intensity interval training group (HIIT); and (d) a high-intensity interval training group adding whole-body electromyostimulation (HIIT + EMS). Results All exercise training modalities induced changes in HRV parameters (all P ≤ 0.001) without statistical differences between them (all P > 0.05). We found associations between changes in body composition and cardiometabolic risk and exercise-related changes in HRV. Conclusion Our results suggest that different exercise interventions (i.e., PAR, HIIT and HIIT + EMS) induced an enhancement of HRV in sedentary middle-aged adults. Our findings support the notion that exercise-related changes in HRV are associated with changes in body composition and cardiometabolic risk after the intervention program Clinical trial registry NCT03334357 (ClinicalTrials.gov). November 7, 2017 retrospectively registered.

Vaginal Microbiota Is Stable and Mainly Dominated by Lactobacillus at Third Trimester of Pregnancy and Active Childbirth: A Longitudinal Study of Ten Mexican Women - Antonio González-Sánchez; José J. Reyes-Lagos; Miguel A. Peña-Castillo; Khemlal Nirmalkar; Jaime García-Mena; Gustavo Pacheco-López (Current Microbiology, 2022)

Evolution and dynamics of the open-vent eruption at Arenal volcano (Costa Rica, 1968–2010): what we learned and perspectives - Mauricio M. Mora; Philippe Lesage; Waldo Taylor-Castillo; Sylvie Vergniolle; Loïc Fourel; Gerardo J. Soto (Bulletin of Volcanology, 2022)
On 29 July 1968, there was a violent reactivation of Arenal volcano. The resulting westward-directed lateral blast eruption left two villages destroyed and 78 people dead. The activity continued as a long-lasting, open-vent eruption that evolved into seven recognisable phases reflecting changes in magma supply, explosive activity and cone evolution, and ended in October 2010. Here, we review this activity, the geophysical approaches applied to understanding it and the open questions resulting from these insights. The eruptive dynamics were characterised by almost constant lava effusion, degassing, strombolian and vulcanian explosions and infrequent pyroclastic density currents. In this study, the total rock dense equivalent volume of lava and tephra erupted is calculated at 757 ± 77 Mm 3 , while the volume of the lava flow field is 527 ± 58 Mm 3 . Typical seismic activity included harmonic and spasmodic tremors, long-period events and explosion signals with frequent audible “booms”. The decline of the eruptive activity started in 2000, with a decrease in the number and size of explosive events, a shift from long to short lava flows along with the collapse of lava flow fronts and the subsequent formation of downward-rolling lava block aprons, the frequent growth of dome-like structures on the summit and a gradual decrease in seismic energy. Multiple geological and geophysical studies during this 42-year-long period of open-vent activity at Arenal resulted in many advances in understanding the dynamics of andesitic blocky lava flows, the origin and diversity of pyroclastic density currents and seismic sources, as well as the role of site effects and rough topography in modifying the seismic wavefield. The acoustic measurements presented here include two types of events: typical explosions and small pressure transients. Features of the latter type are not usually observed at volcanoes with intermediate to evolved magma composition. Explosions have different waveforms and larger gas volumes than pressure transients, both types being associated with active and passive degassing, respectively. This body of data, results and knowledge can inform on the type of activity, and associated geophysical signals, of open-vent systems that are active for decades.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Correction to: A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

A study on correlations between precipitation ETCCDI and airborne pollen/fungal spore parameters in the NE Iberian Peninsula - R. Rodríguez-Solà; M. C. Casas-Castillo; J. J. Ho Zhang; R. Kirchner; M. Alarcón; C. Periago; C. De Linares; J. Belmonte (International Journal of Biometeorology, 2022)

Micropropagation of Catasetum integerrimum Hook (Orchidaceae) through seed germination and direct shoot regeneration from pseudobulbs and roots - Luis J. Castillo-Pérez; Angel Josabad Alonso-Castro; Javier Fortanelli-Martínez; Candy Carranza-Álvarez (In Vitro Cellular & Developmental Biology - Plant, 2022)

Genomics outperforms genetics to manage mistakes in fisheries stocking of threatened species - Catherine R. M. Attard; Jonathan Sandoval-Castillo; Dean M. Gilligan; Peter J. Unmack; Leanne K. Faulks; Luciano B. Beheregaray (Biodiversity and Conservation, 2022)
Hatchery production and fisheries stocking is a widespread and high profile management practice because it allows recreational fisheries to continue in threatened species. Human-mediated transfer of fish across the geographic boundaries of intraspecies lineages or closely related species can cause introgression and occasionally outbreeding depression. Hybridization can be difficult to detect due to limited morphological differences among close lineages and the relatively low power of traditional genetic datasets. Here we showcase the use of genomic techniques to detect admixture of the economically important and threatened golden perch ( Macquaria ambigua ) in the Murray-Darling Basin, southeast Australia. We detected admixture through a genome-wide dataset of 6,862 single nucleotide polymorphisms (SNPs) across 174 Murray-Darling sourced fish and 15 fish from each of two neighbouring basins: the Lake Eyre and Fitzroy basins. Individuals with partial ancestry from both neighboring basins were detected using genomics throughout the Murray-Darling, suggesting the release of individuals and introgression into the Murray-Darling Basin. Importantly, a traditional microsatellite dataset was unreliable for identifying admixed individuals. The SNP-detected admixed individuals were also found in Murray-Darling impoundments, where fish are solely sourced from government-managed hatcheries, suggesting that some broodstock in hatcheries might have non-endemic ancestry. Stocking programs for golden perch release over one million fingerlings each year, and so could impact the genetic variation in the wild. We advocate for using genomics to check the ancestry of broodstock and for increasing collaboration between managers and academics—as done here—to better integrate the power of genomics into biodiversity management and conservation.

Anti-trypanosomal screening of Salvadoran flora - Ulises G. Castillo; Ayato Komatsu; Morena L. Martínez; Jenny Menjívar; Marvin J. Núñez; Yoshinori Uekusa; Yuji Narukawa; Fumiyuki Kiuchi; Junko Nakajima-Shimada (Journal of Natural Medicines, 2022)
Chagas disease is caused by the protozoan parasite Trypanosoma cruzi , and in Central America, it is considered one of the four most infectious diseases. This study aimed to screen the anti-trypanosomal activity of plant species from Salvadoran flora. Plants were selected through literature search for plants ethnobotanically used for antiparasitic and Chagas disease symptomatology, and reported in Museo de Historia Natural de El Salvador (MUHNES) database. T. cruzi was incubated for 72 h with 2 different concentrations of methanolic extracts of 38 species, among which four species, Piper jacquemontianum , Piper lacunosum , Trichilia havanensis , and Peperomia pseudopereskiifolia , showed the activity (≤ 52.0% viability) at 100 µg/mL. Separation of the methanolic extract of aerial parts from Piper jacquemontianum afforded a new flavanone ( 4 ) and four known compounds, 2,2-dimethyl-6-carboxymethoxychroman-4-one ( 1 ), 2,2-dimethyl-6-carboxychroman-4-one ( 2 ), cardamomin ( 3 ), and pinocembrin ( 5 ), among which cardamomin exhibited the highest anti-trypanosomal activity (IC 50 = 66 µM). Detailed analyses of the spectral data revealed that the new compound 4 , named as jaqueflavanone A, was a derivative of pinocembrin having a prenylated benzoate moiety at the 8-position of the A ring. Graphic abstract

Giant Toads (Rhinella marina) From the Industrial Zones of Low Basin of the Coatzacoalcos River (Veracruz, MX) Presents Genotoxicity in Erythrocytes - Omar Cruz-Santiago; Claudia G. Castillo; Guillermo Espinosa-Reyes; Iván N. Pérez-Maldonado; Donaji J. González-Mille; María del Carmen Cuevas-Díaz; César A. Ilizaliturri-Hernández (Bulletin of Environmental Contamination and Toxicology, 2022)

Autosomal Recessive Cerebellar Ataxia 1: First Case Report Depicting a Variant in SYNE1 Gene in a Chilean Patient - J Valentina Castillo; S Catherine Díaz; María Leonor Bustamante; Matheus Gomes Ferreira; Hélio A. G. Teive; Marcelo Miranda (The Cerebellum, 2021)

The Standard Deviation Structure as a New Approach to Growth Analysis in Weight and Length Data of Farmed Lutjanus guttatus - Sergio G. Castillo-Vargasmachuca; Eugenio Alberto Aragón-Noriega; Guillermo Rodríguez-Domínguez; Leonardo Martínez-Cárdenas; Eulalio Arámbul-Muñoz; Álvaro J. Burgos Arcos (Fishes, 2021)
In the present study, size-at-age data (length and weight) of marine cage-reared spotted rose snapper Lutjanus guttatus were analyzed under four different variance assumptions (observed, constant, depensatory, and compensatory variances) to analyze the robustness of selecting the right standard deviation structure to parametrize the von Bertalanffy, Logistic, and Gompertz models. The selection of the best model and variance criteria was obtained based on the Bayesian information criterion (BIC). According to the BIC results, the observed variance in the present study was the best way to parametrize the three abovementioned growth models, and the Gompertz model best represented the length and weight growth curves. Based on these results, using the observed error structure to calculate the growth parameters in multi-model inference analyses is recommended.

Identification and characterization of a new cry-like gene found in a Bacillus cereus strain - J. Francisco Castillo-Esparza; Javier Luévano-Borroel; Jorge E. Ibarra (Antonie van Leeuwenhoek, 2021)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Veronia nyctiphanis gen. nov., sp. nov., Isolated from the Stomach of the Euphausiid Nyctiphanes simplex (Hansen, 1911) in the Gulf of California, and Reclassification of Enterovibrio pacificus as Veronia pacifica comb. nov. - Bruno Gomez-Gil; Adrián González-Castillo; Mario J. Aguilar-Méndez; Alejandro López-Cortés; Jaime Gómez-Gutiérrez; Ana Roque; Elke Lang; Julissa Enciso-Ibarra (Current Microbiology, 2021)

Phylogeography of Habia fuscicauda (Cardinalidae) indicates population isolation, genetic divergence and demographic changes during the Quaternary climate shifts in the Mesoamerican rainforest - Vicente de J. Castillo-Chora; Luz E. Zamudio-Beltrán; Carmen Pozo; Blanca E. Hernández-Baños (Journal of Ornithology, 2021)

Salinity and inundation effects on Iris pseudacorus: implications for tidal wetland invasion with sea level rise - Brenda J. Grewell; Blanca Gallego-Tévar; Morgane B. Gillard; Caryn J. Futrell; Rebecca Reicholf; Jesús M. Castillo (Plant and Soil, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Asymbiotic seed germination, in vitro seedling development, and symbiotic acclimatization of the Mexican threatened orchid Stanhopea tigrina - Luis J. Castillo-Pérez; Domingo Martínez-Soto; Javier Fortanelli-Martínez; Candy Carranza-Álvarez (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

The effects of three types of exercise training on steroid hormones in physically inactive middle-aged adults: a randomized controlled trial - Manuel Dote-Montero; Alejandro De-la-O; Lucas Jurado-Fasoli; Jonatan R. Ruiz; Manuel J. Castillo; Francisco J. Amaro-Gahete (European Journal of Applied Physiology, 2021)

Two offshore coral species show greater acclimatization capacity to environmental variation than nearshore counterparts in southern Belize - J. H. Baumann; C. B. Bove; L. Carne; I. Gutierrez; K. D. Castillo (Coral Reefs, 2021)

Mitochondrial DNA genome evidence for the existence of a third divergent lineage in the western Atlantic Ocean for the bull shark ( Carcharhinus leucas ) - Nadia Sandoval Laurrabaquio‐Alvarado; Píndaro Díaz‐Jaimes; Silvia Hinojosa‐Álvarez; Maria del Pilar Blanco‐Parra; Douglas H. Adams; Juan Carlos Pérez‐Jiménez; J. Leonardo Castillo‐Géniz (Journal of Fish Biology, 2021)
We report for the first time a highly divergent lineage in the Caribbean Sea for the bull shark ( Carcharhinus leucas ) based on the analysis of 51 mitochondrial DNA genomes of individuals collected in the western North Atlantic. When comparing the mtDNA control region obtained from the mitogenomes to sequences reported previously for Brazil, the Caribbean lineage remained highly divergent. These results support the existence of a discrete population in Central America due to a phylogeographic break separating the Caribbean Sea from the western North Atlantic, Gulf of Mexico and South America.

Seed bank dynamics of the annual halophyte Salicornia ramosissima: towards a sustainable exploitation of its wild populations - Alejandro Polo; Alba Fragoso; María D. Infante-Izquierdo; Francisco J. J. Nieva; Adolfo F. Muñoz-Rodríguez; Jesús M. Castillo (Plant Ecology, 2021)

Streptomyces sp. M54: an actinobacteria associated with a neotropical social wasp with high potential for antibiotic production - Bernal Matarrita-Carranza; Catalina Murillo-Cruz; Roberto Avendaño; María Isabel Ríos; Max Chavarría; María Luisa Gómez-Calvo; Giselle Tamayo-Castillo; Juan J. Araya; Adrián A. Pinto-Tomás (Antonie van Leeuwenhoek, 2021)

Quantifying the Impact on Stormwater Management of an Innovative Ceramic Permeable Pavement Solution - Jesica Tamara Castillo-Rodríguez; I. Andrés-Doménech; M. Martín; I. Escuder-Bueno; S. Perales-Momparler; J. Mira-Peidro (Water Resources Management, 2021)

Potential distribution of the dinoflagellate Peridinium quadridentatum and its blooms in continental shelves globally: an environmental and geographic approach - Carlos F. Rodríguez-Gómez; Gabriela Vázquez; Carlos A. Maya-Lastra; José A. Aké-Castillo; Christine J. Band-Schmidt; Patricia Moreno-Casasola; Octavio Rojas-Soto (Marine Biology, 2021)

Variation in sexual reproductive output among exotic taxa of Spartina (Poaceae) - M. Dolores Infante-Izquierdo; Adolfo. F. Muñoz-Rodríguez; F. Javier J. Nieva; Alejandro Polo-Ávila; Enrique Sánchez-Gullón; Jesús J. Soriano; Israel Sanjosé; Brenda J. Grewell; Jesús M. Castillo (Aquatic Ecology, 2021)

A Matter of Scale: Population Genomic Structure and Connectivity of Fisheries At-Risk Common Dolphins (Delphinus delphis) From Australasia - Andrea Barceló; Jonathan Sandoval-Castillo; Karen A. Stockin; Kerstin Bilgmann; Catherine R. M. Attard; Nikki Zanardo; Guido J. Parra; Krista Hupman; Isabella M. Reeves; Emma L. Betty; Gabriela Tezanos-Pinto; Luciano B. Beheregaray; et al. (Frontiers in Marine Science, 2021)
An understanding of population structure and connectivity at multiple spatial scales is required to assist wildlife conservation and management. This is particularly critical for widely distributed and highly mobile marine mammals subject to fisheries by-catch. Here, we present a population genomic assessment of a near-top predator, the common dolphin ( Delphinus delphis ), which is incidentally caught in multiple fisheries across the Australasian region. The study was carried out using 14,799 ddRAD sequenced genome-wide markers genotyped for 478 individuals sampled at multiple spatial scales across Australasia. A complex hierarchical metapopulation structure was identified, with three highly distinct and genetically diverse regional populations at large spatial scales (>1,500 km). The populations inhabit the southern coast of Australia, the eastern coast of Australia, New Zealand, and Tasmania, with the latter also showing a considerable level of admixture to Australia's east coast. Each of these regional populations contained two to four nested local populations (i.e., subpopulations) at finer spatial scales, with most of the gene flow occurring within distances of 50 to 400 km. Estimates of contemporary migration rates between adjacent subpopulations ranged from 6 to 25%. Overall, our findings identified complex common dolphin population structure and connectivity across state and international jurisdictions, including migration and gene flow across the Tasman Sea. The results indicate that inter-jurisdictional collaboration is required to implement conservation management strategies and mitigate fisheries interactions of common dolphins across multiple spatial scales in the Australasian region.

Recovery of Fuels Using the Supramolecular Gelation Ability of a Hydroxybenzoic Acid Bisamide Derivative - Samuel Zapién-Castillo; Jorge Jesús Montes-Patiño; Josué Francisco Pérez-Sánchez; Jessica Ismalé Lozano-Navarro; José Aarón Melo-Banda; Philippe J. Mésini; Nancy Patricia Díaz-Zavala (Water, Air, & Soil Pollution, 2021)

Human health risks from fish consumption following a catastrophic gas oil spill in the Chiquito River, Veracruz, Mexico - Randy H. Adams; Valeria Ojeda-Castillo; Francisco J. Guzmán-Osorio; Gerónimo Álvarez-Coronel; Verónica Isidra Domínguez-Rodríguez (Environmental Monitoring and Assessment, 2020)

Prior cortical activity differences during an action observation plus motor imagery task related to motor adaptation performance of a coordinated multi-limb complex task - J. Ignacio Serrano; Daniel Muñoz-García; Raúl Ferrer-Peña; Victor D’eudeville; Marta Brero; Maxime Boisson; M. Dolores del Castillo (Cognitive Neurodynamics, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Genetic diversity of coffee (Coffea spp.) in Mexico evaluated by using DArTseq and SNP markers - J. L. Spinoso-Castillo; E. Escamilla-Prado; V. H. Aguilar-Rincón; V. Morales Ramos; G. García de los Santos; P. Pérez-Rodríguez; T. Corona-Torres (Genetic Resources and Crop Evolution, 2020)

Object-Based Image Analysis Using Harmonic Analysis on A High-Spatial Resolution Satellite Image - Oscar Castillo; James J. Hayes (International Journal of Remote Sensing, 2020)

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Assessing seed desiccation responses of native trees in the Caribbean - Efisio Mattana; Brígido Peguero; Alice Di Sacco; Wilvin Agramonte; Wilkin Rafael Encarnación Castillo; Francisco Jiménez; Teodoro Clase; Hugh W. Pritchard; Pablo Gómez-Barreiro; Elena Castillo-Lorenzo; Marianny Terrero Encarnación; Michael J. Way; et al. (New Forests, 2020)
Native trees from the Caribbean were tested for seed desiccation responses, by adapting the “100-seed test” protocol. Ninety-seven seed lots of 91 species were collected in the Dominican Republic and tested for germination immediately after collecting, and after drying and moist storage. Seed desiccation sensitivity was assessed as a continuous variable (Viability Loss Index; VLI), based on seed germination values before and after drying. The results were compared with predictions of seed desiccation responses based on seed lot traits (initial moisture content and thousand-seed weight) and with those of published predictive models based on plant and seed traits. VLI could be calculated for seed lots of 40 species. 80% of these seed lots showed consistent results among experiments and predictive models. Issues on the set up of the experiments were discussed, as well as the species for which experimental results and predictions led to contrasting results. Overall, the “100-seed test” confirmed to be an effective tool for assessing seed desiccation responses of a diverse under-investigated woody flora, guiding the seed conservation of trees and their use in reforestation programmes. In addition, by providing new data, it might improve the performance of available predictive models.

A New Species of Moth Lacewing from the Mesoamerican Genus Adamsiana Penny 1996 (Neuroptera: Ithonidae) - A. Ardila-Camacho; R. Castillo-Argaez; J. I. Martínez (Neotropical Entomology, 2020)

Heavy metals (lead, cadmium and zinc) from street dust in Monterrey, Mexico: ecological risk index - D. Castillo-Nava; M. Elias-Santos; U. J. López-Chuken; A. Valdés-González; L. G. de la Riva-Solís; M. P. Vargas-Pérez; L. J. Galán-Wong; H. A. Luna-Olvera (International Journal of Environmental Science and Technology, 2020)

White-Faced Capuchin, Cebus capucinus imitator, Hammerstone and Anvil Tool Use in Riparian Habitats on Coiba Island, Panama - Claudio M. Monteza-Moreno; Tamara Dogandžić; Kevin A. McLean; Pedro L. Castillo-Caballero; Zarluis Mijango-Ramos; Evelyn Del Rosario-Vargas; Margaret C. Crofoot; Brendan J. Barrett (International Journal of Primatology, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Fruit Set, Seed Viability and Germination of the European Native Spartina maritima in Southwest Iberian Peninsula - M. Dolores Infante-Izquierdo; Jesús M. Castillo; F. Javier J. Nieva; Ioana D. Rotundu; Francesca T. David; Brenda J. Grewell; Adolfo F. Muñoz-Rodríguez (Wetlands, 2020)

In vitro and in silico evaluations of new aryloxy-1,4-naphthoquinones as anti-Trypanosoma cruzi agents - Alejandra González; Nohemí Becerra; Muhammad Kashif; Mercedes González; Hugo Cerecetto; Elena Aguilera; Benjamín Nogueda-Torres; Karla F. Chacón-Vargas; J. José Zarate-Ramos; Uziel Castillo-Velázquez; Cristian O. Salas; Gildardo Rivera; et al. (Medicinal Chemistry Research, 2020)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Synthesis, in vitro antigiardial activity, SAR analysis and docking study of substituted chalcones - David Cáceres-Castillo; Rubén M. Carballo; Ramiro Quijano-Quiñones; Gumersindo Mirón-López; Manlio Graniel-Sabido; Rosa E. Moo-Puc; Gonzalo J. Mena-Rejón (Medicinal Chemistry Research, 2020)

Clinical isolates of Escherichia coli are resistant both to antibiotics and organotin compounds - M. Aguilar-Santelises; J. Castillo-Vera; R. Gonzalez-Molina; A. Garcia del Valle; M. Cruz Millan; L. Aguilar-Santelises (Folia Microbiologica, 2020)

Growth, forage yield and quality of Morus alba L. and Gliricidia sepium (Jacq.) Walp. in mixed and pure fodder bank systems in Yucatan, México - Olivier S. Ramos-Trejo; Jorge R. Canul-Solís; Azucena del R. Alvarado-Canché; Luis E. Castillo-Sánchez; Juan J. Sandoval-Gío; María J. Campos-Navarrete; Angel T. Piñeiro-Vázquez; Alfonso J. Chay-Canul; Fernando Casanova-Lugo (Agroforestry Systems, 2020)

Lanthanum- and cerium-based functionalization of chars and activated carbons for the adsorption of fluoride and arsenic ions - E. E. Merodio-Morales; H. E. Reynel-Ávila; D. I. Mendoza-Castillo; C. J. Duran-Valle; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2020)

Utilization of naproxen by Amycolatopsis sp. Poz 14 and detection of the enzymes involved in the degradation metabolic pathway - B. M. Alanis-Sánchez; S. M. Pérez-Tapia; S. Vázquez-Leyva; I. Mejía-Calvo; Z. Macías-Palacios; L. Vallejo-Castillo; C. M. Flores-Ortiz; C. Guerrero-Barajas; J. A. Cruz-Maya; J. Jan-Roblero (World Journal of Microbiology and Biotechnology, 2019)

Availability of copper in mine tailings with humic substance addition and uptake by Atriplex halimus - Y. Tapia; M. Casanova; B. Castillo; E. Acuña; J. Covarrubias; M. Antilén; A. Masaguer (Environmental Monitoring and Assessment, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

ENSO and NAO affect long‐term leaf litter dynamics and stoichiometry of Scots pine and European beech mixedwoods - Ester González de Andrés; Juan A. Blanco; J. Bosco Imbert; Biing T. Guan; Yueh‐Hsin Lo; Federico J. Castillo (Global Change Biology, 2019)
Litterfall dynamics (production, seasonality and nutrient composition) are key factors influencing nutrient cycling. Leaf litter characteristics are modified by species composition, site conditions and water availability. However, significant evidence on how large‐scale, global circulation patterns affect ecophysiological processes at tree and ecosystem level remains scarce due to the difficulty in separating the combined influence of different factors on local climate and tree phenology. To fill this gap, we studied links between leaf litter dynamics with climate and other forest processes, such as tree‐ring width (TRW) and intrinsic water‐use efficiency (iWUE) in two mixtures of Scots pine ( Pinus sylvestris L.) and European beech ( Fagus sylvatica L.) in the south‐western Pyrenees. Temporal series (18 years) of litterfall production and elemental chemical composition were decomposed following the ensemble empirical mode decomposition method and relationships with local climate, large‐scale climatic indices, TRW and Scots pine's iWUE were assessed. Temporal trends in N:P ratios indicated increasing P limitation of soil microbes, thus affecting nutrient availability, as the ecological succession from a pine‐dominated to a beech‐dominated forest took place. A significant influence of large‐scale patterns on tree‐level ecophysiology was explained through the impact of the North Atlantic Oscillation (NAO) and El Niño–Southern Oscillation (ENSO) on water availability. Positive NAO and negative ENSO were related to dry conditions and, consequently, to early needle shedding and increased N:P ratio of both species. Autumn storm activity appears to be related to premature leaf abscission of European beech. Significant cascading effects from large‐scale patterns on local weather influenced pine TRW and iWUE. These variables also responded to leaf stoichiometry fallen 3 years prior to tree‐ring formation. Our results provide evidence of the cascading effect that variability in global climate circulation patterns can have on ecophysiological processes and stand dynamics in mixed forests.

Diffuse Hydrothermal Venting: A Hidden Source of Iron to the Oceans - Alastair J. M. Lough; Douglas P. Connelly; William B. Homoky; Jeffrey A. Hawkes; Valerie Chavagnac; Alain Castillo; Majid Kazemian; Ko-ichi Nakamura; Tohru Araki; Burkhard Kaulich; Rachel A. Mills (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pattern Recognition Applied to Attenuation of Multiples in Subsalt Imaging - J. C. Ortiz-Alemán; J. Abreu-Torres; M. G. Orozco-del-Castillo; J. J. Hernández-Gómez (Pure and Applied Geophysics, 2019)

The BeWo cell line derived from a human placental choriocarcinoma is permissive for respiratory syncytial virus infection - M. A. Velázquez-Cervantes; M. Martínez-Castillo; L. D. González-García; T. A. Vargas-Pavía; M. G. Martínez-Salazar; I. Mancilla-Herrera; G. León-Reyes; J. García-Cordero; A. C. Helguera-Repetto; M. León-Juárez (Virus Genes, 2019)

Echeveria sonianevadensis (Crassulaceae), una nueva especie del Volcán Nevado de Colima del occidente de México y una clave para la serie Gibbiflorae - H. David Jimeno-Sevilla; J. Antonio Vázquez-García; Miguel Ángel Muñiz-Castro; Ignacio García-Ruiz; Gerardo Hernández-Vera; y José Villa Castillo (Brittonia, 2019)

Description of Ornithodoros montensis n. sp. (Acari, Ixodida: Argasidae), a parasite of the toad Rhinella arenarum (Amphibia, Anura: Bufonidae) in the Monte Desert of Argentina - José M. Venzal; Gabriel N. Castillo; Cynthia J. Gonzalez-Rivas; Atilio J. Mangold; Santiago Nava (Experimental and Applied Acarology, 2019)

The role of collectivism in modeling the adoption of renewable energies: a cross-cultural approach - E. Higueras-Castillo; F. J. Liébana-Cabanillas; F. Muñoz-Leiva; S. Molinillo (International Journal of Environmental Science and Technology, 2019)

Determination of ractopamine residue in tissues and urine from pig fed meat and bone meal - Carolina N. Aroeira; Vivian Feddern; Vanessa Gressler; Luciano Molognoni; Heitor Daguer; Osmar A. Dalla Costa; Gustavo J.M.M. de Lima; Carmen J. Contreras-Castillo (Food Additives & Contaminants: Part A, 2019)

A New Species of Vindex Kaup (Coleoptera: Scarabaeoidea: Passalidae: Passalinae: Proculini) from Oaxaca, Mexico - E. R. Ariza-Marín; P. Reyes-Castillo; V. Moctezuma; J. L. Sánchez-Huerta (Neotropical Entomology, 2019)

Apparent timing of density banding in the Caribbean coral Siderastrea siderea suggests complex role of key physiological variables - B. E. Benson; J. P. Rippe; C. B. Bove; K. D. Castillo (Coral Reefs, 2019)

The endemic orchids of Mexico: a review - Luis J. Castillo-Pérez; Domingo Martínez-Soto; Juan J. Maldonado-Miranda; Angel J. Alonso-Castro; Candy Carranza-Álvarez (Biologia, 2019)

Web-based tool for calculating field-specific nutrient management for rice in India - Sheetal Sharma; P. Panneerselvam; Rowena Castillo; Shriram Manohar; Rajendran Raj; V. Ravi; Roland J. Buresh (Nutrient Cycling in Agroecosystems, 2019)

Surface impurities on giant gypsum crystals from “la Cueva de las Espadas” (Cave of Swords), Naica, Mexico - Isaí Castillo-Sandoval; Luis E. Fuentes-Cobas; Bernardo E. Pérez-Cazares; Hilda E. Esparza-Ponce; María E. Fuentes-Montero; Hiram Castillo-Michel; Diane Eichert; Ignacio Reyes-Cortes; Iván J. Carreño-Márquez; José M. Napoles-Duarte; María E. Montero-Cabrera (Mineralogy and Petrology, 2018)

Realized niche and spatial pattern of native and exotic halophyte hybrids - B. Gallego-Tévar; G. Curado; B. J. Grewell; M. E. Figueroa; J. M. Castillo (Oecologia, 2018)

Northernmost Occurrence of Zanclus cornutus (Zanclidae) in the Eastern Pacific (Northern Gulf of California, Mexico) - Francisco J. Fernández-Rivera Melo; Héctor Reyes-Bonilla; Violeta Martínez-Castillo; Fernanda Pérez-Alarcón (Thalassas: An International Journal of Marine Sciences, 2018)

Passalidae (Coleoptera: Scarabaeoidea) of the Biogeographical Province of Chocó and the West Andean Region of Colombia, with the Description of Two New Species - L Jiménez-Ferbans; P Reyes-Castillo; J C Schuster (Neotropical Entomology, 2018)

Logging Pattern and Landscape Change in Southern Mexico: Identifying Potential Weaknesses and Strengthening Conservation in Community-Based Management Programs through Landscape Analysis - J A Ascanio-Lárraga; J L León-Cortés; M A Castillo-Santiago; E Ramírez-Segura (Journal of Forestry, 2018)

Secondary metabolites from two Hispaniola Ageratina species and their cytotoxic activity - José Luis Eiroa; Jorge Triana; Francisco J. Pérez; Quírico A. Castillo; Ignacio Brouard; José Quintana; Francisco Estévez; Francisco León (Medicinal Chemistry Research, 2018)

Using unmanned aerial vehicle (UAV) surveys and image analysis in the study of large surface‐associated marine species: a case study on reef sharks Carcharhinus melanopterus shoaling behaviour - Guillaume Rieucau; Jeremy J. Kiszka; Jose Carlos Castillo; Johann Mourier; Kevin M. Boswell; Michael R. Heithaus (Journal of Fish Biology, 2018)
A novel image analysis‐based technique applied to unmanned aerial vehicle (UAV) survey data is described to detect and locate individual free‐ranging sharks within aggregations. The method allows rapid collection of data and quantification of fine‐scale swimming and collective patterns of sharks. We demonstrate the usefulness of this technique in a small‐scale case study exploring the shoaling tendencies of blacktip reef sharks Carcharhinus melanopterus in a large lagoon within Moorea, French Polynesia. Using our approach, we found that C. melanopterus displayed increased alignment with shoal companions when distributed over a sandflat where they are regularly fed for ecotourism purposes as compared with when they shoaled in a deeper adjacent channel. Our case study highlights the potential of a relatively low‐cost method that combines UAV survey data and image analysis to detect differences in shoaling patterns of free‐ranging sharks in shallow habitats. This approach offers an alternative to current techniques commonly used in controlled settings that require time‐consuming post‐processing effort.

Pharmacological dissection of the cellular mechanisms associated to the spontaneous and the mechanically stimulated ATP release by mesentery endothelial cells: roles of thrombin and TRPV - M. Verónica Donoso; Felipe Hernández; Tania Villalón; Claudio Acuña-Castillo; J. Pablo Huidobro-Toro (Purinergic Signalling, 2018)

Dynamic fuzzy neural network for simulating the fixed-bed adsorption of cadmium, nickel, and zinc on bone char - F. A. Gordillo-Ruíz; F. J. Sánchez-Ruíz; D. I. Mendoza-Castillo; H. E. Reynel-Ávila; A. Bonilla-Petriciolet (International Journal of Environmental Science and Technology, 2018)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

In situ toxicity and ecological risk assessment of agro-pesticide runoff in the Madre de Dios River in Costa Rica - Silvia Echeverría-Sáenz; Freylan Mena; María Arias-Andrés; Seiling Vargas; Clemens Ruepert; Paul J. Van den Brink; Luisa E. Castillo; Jonas S. Gunnarsson (Environmental Science and Pollution Research, 2018)

Environmental risk assessment of pesticides in the River Madre de Dios, Costa Rica using PERPEST, SSD, and msPAF models - Robert A. Rämö; Paul J. van den Brink; Clemens Ruepert; Luisa E. Castillo; Jonas S. Gunnarsson (Environmental Science and Pollution Research, 2018)

Forest resilience to drought varies across biomes - Antonio Gazol; Jesus Julio Camarero; Sergio M. Vicente‐Serrano; Raúl Sánchez‐Salguero; Emilia Gutiérrez; Martin de Luis; Gabriel Sangüesa‐Barreda; Klemen Novak; Vicente Rozas; Pedro A. Tíscar; Juan C. Linares; Natalia Martín‐Hernández; et al. (Global Change Biology, 2018)
Forecasted increase drought frequency and severity may drive worldwide declines in forest productivity. Species‐level responses to a drier world are likely to be influenced by their functional traits. Here, we analyse forest resilience to drought using an extensive network of tree‐ring width data and satellite imagery. We compiled proxies of forest growth and productivity ( TRW i, absolutely dated ring‐width indices; NDVI , Normalized Difference Vegetation Index) for 11 tree species and 502 forests in Spain corresponding to Mediterranean, temperate, and continental biomes. Four different components of forest resilience to drought were calculated based on TRW i and NDVI data before, during, and after four major droughts (1986, 1994–1995, 1999, and 2005), and pointed out that TRW i data were more sensitive metrics of forest resilience to drought than NDVI data. Resilience was related to both drought severity and forest composition. Evergreen gymnosperms dominating semi‐arid Mediterranean forests showed the lowest resistance to drought, but higher recovery than deciduous angiosperms dominating humid temperate forests. Moreover, semi‐arid gymnosperm forests presented a negative temporal trend in the resistance to drought, but this pattern was absent in continental and temperate forests. Although gymnosperms in dry Mediterranean forests showed a faster recovery after drought, their recovery potential could be constrained if droughts become more frequent. Conversely, angiosperms and gymnosperms inhabiting temperate and continental sites might have problems to recover after more intense droughts since they resist drought but are less able to recover afterwards.

Single-cell PCR amplification of thecate dinoflagellates: a case study of Tripos (Dinophyceae) - A. Hernández-Rosas; M. E. Meave del Castillo; J. Díaz-Larrea; F. Rodríguez (Journal of Applied Phycology, 2018)

Glycemic response after glucose oral administration of wild juvenile red grouper Epinephelus morio fed two different diets - A. Castillo; A. Alvarez; G. Cuzon; J. Suárez; G. Gaxiola (Fish Physiology and Biochemistry, 2018)

Ocean–atmosphere conditions related to severe and persistent droughts in the Mexican Altiplano - José Pablo Vega‐Camarena; Luis Brito‐Castillo; Luis M. Farfán; David J. Gochis; Luis F. Pineda‐Martínez; Sara C. Díaz (International Journal of Climatology, 2018)
Ocean and atmospheric patterns associated with the most severe and most persistent droughts in the Mexican Altiplano region are explored. The standardized precipitation index on a time scale of 12 months was used and compared with time series of other atmospheric conditions to identify major dry episodes from 1970 to 2012. The time series were derived from the second mode of a varimax‐rotated empirical orthogonal functional analysis from the mean summer rainfall series observed at weather stations located in the Mexican Altiplano from 1970 through 2000. The results showed that the longest and most persistent episode occurred from 1998 through 2001, while the most severe dry episode occurred in 2011–2012, when the Pacific Decadal Oscillation was in a negative phase and the Atlantic Multidecadal Oscillation in a positive phase, both in combination with a La Niña event. A large upper‐level anticyclone over the north‐central United States is related to droughts in the Altiplano. Under these conditions, the droughts were linked to a large anticyclone positioned over the central‐north of the United States, with consequent negative anomalies of specific humidity over central‐northern Mexico. Concurrent with droughts in the interior of Mexico, are positive rainfall anomalies along the central Pacific coast of Mexico near the study area. Under different atmospheric conditions, opposite anomalous behaviour between the coast and interior can exist. The mechanism driving this see‐saw behaviour between the west coast of Mexico and the Altiplano is explored.

Ecological disturbance influences adaptive divergence despite high gene flow in golden perch ( Macquaria ambigua ): Implications for management and resilience to climate change - Catherine R. M. Attard; Chris J. Brauer; Jonathan Sandoval‐Castillo; Leanne K. Faulks; Peter J. Unmack; Dean M. Gilligan; Luciano B. Beheregaray (Molecular Ecology, 2018)
Populations that are adaptively divergent but maintain high gene flow may have greater resilience to environmental change as gene flow allows the spread of alleles that have already been tested elsewhere. In addition, populations naturally subjected to ecological disturbance may already hold resilience to future environmental change. Confirming this necessitates ecological genomic studies of high dispersal, generalist species. Here we perform one such study on golden perch ( Macquaria ambigua ) in the Murray‐Darling Basin ( MDB ), Australia, using a genome‐wide SNP data set. The MDB spans across arid to wet and temperate to subtropical environments, with low to high ecological disturbance in the form of low to high hydrological variability. We found high gene flow across the basin and three populations with low neutral differentiation. Genotype–environment association analyses detected adaptive divergence predominantly linked to an arid region with highly variable riverine flow, and candidate loci included functions related to fat storage, stress and molecular or tissue repair. The high connectivity of golden perch in the MDB will likely allow locally adaptive traits in its most arid and hydrologically variable environment to spread and be selected in localities that are predicted to become arid and hydrologically variable in future climates. High connectivity in golden perch is likely due to their generalist life history and efforts of fisheries management. Our study adds to growing evidence of adaptation in the face of gene flow and highlights the importance of considering ecological disturbance and adaptive divergence in biodiversity management.

Induced Degradation of Anthraquinone-Based Dye by Laccase Produced from Pycnoporus sanguineus (CS43) - Michelle Salazar-López; Magdalena de J. Rostro-Alanis; Carlos Castillo-Zacarías; Ana L. Parra-Guardado; Carlos Hernández-Luna; Hafiz M. N. Iqbal; Roberto Parra-Saldivar (Water, Air, & Soil Pollution, 2017)

Monitoring of landslide displacements using UAS and control methods based on lines - A. T. Mozas-Calvache; J. L. Pérez-García; T. Fernández-del Castillo (Landslides, 2017)

Prognostic accuracy of SIRS criteria, qSOFA score and GYM score for 30-day-mortality in older non-severely dependent infected patients attended in the emergency department - J. González del Castillo; A. Julian-Jiménez; F. González-Martínez; J. Álvarez-Manzanares; P. Piñera; C. Navarro-Bustos; M. Martinez-Ortiz de Zarate; F. Llopis-Roca; M. Debán Fernández; J. Gamazo-Del Rio; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Impact of severe hematological abnormalities in the outcome of hospitalized patients with influenza virus infection - A. Lalueza; H. Trujillo; J. Laureiro; B. Ayuso; P. Hernández-Jiménez; C. Castillo; M. Torres; D. Folgueira; O. Madrid; C. Díaz-Pedroche; E. Arrieta; C. Arévalo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Predictive score of haematological toxicity in patients treated with linezolid - J. González-Del Castillo; F. J. Candel; R. Manzano-Lorenzo; L. Arias; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prevalence, geographic distribution and phenotypic differences of Piscirickettsia salmonis EM ‐90‐like isolates - J Saavedra; N Hernandez; A Osses; A Castillo; A Cancino; H Grothusen; E Navas; P Henriquez; H Bohle; F Bustamante; P Bustos; M Mancilla (Journal of Fish Diseases, 2017)
Early reports accounted for two main genotypes of Piscirickettsia salmonis , a fish pathogen and causative agent of piscirickettsiosis, placing the single isolate EM ‐90 apart from the prototypic LF ‐89 and related isolates. In this study, we provide evidence that, contrary to what has been supposed, the EM ‐90‐like isolates are highly prevalent and disseminated across Chilean marine farms. Molecular analysis of 507 P. salmonis field isolates derived from main rearing areas, diverse hosts and collected over 6 years, revealed that nearly 50% of the entire collection were indeed typed as EM ‐90‐like. Interestingly, these isolates showed a marked host preference, being recovered exclusively from Atlantic salmon ( Salmo salar ) samples. Although both strains produce undistinguishable pathological outcomes, differences regarding growth kinetics and susceptibility to the antibiotics and bactericidal action of serum could be identified. In sum, our results allow to conclude that the EM ‐90‐like isolates represent an epidemiologically relevant group in the current situation of piscirickettsiosis. Based on the consistency between genotype and phenotype exhibited by this strain, we point out the need for genotypic studies that may be as important for the Chilean salmon industry as the continuous surveillance of antimicrobial susceptibility patterns.

A simulation tool for advanced design and management of collective sprinkler-irrigated areas: a study case - N. Zapata; E. H. El Malki; B. Latorre; J. Gallinat; F. J. Citoler; R. Castillo; E. Playán (Irrigation Science, 2017)

Hexavalent chromium bioreduction and chemical precipitation of sulphate as a treatment of site-specific fly ash leachates - Errol D. Cason; Peter J. Williams; Elizabeth Ojo; Julio Castillo; Mary F. DeFlaun; Esta van Heerden (World Journal of Microbiology and Biotechnology, 2017)

Antimicrobial and hormetic effects of silver nanoparticles on in vitro regeneration of vanilla (Vanilla planifolia Jacks. ex Andrews) using a temporary immersion system - J. L. Spinoso-Castillo; R. A. Chavez-Santoscoy; Nina Bogdanchikova; J. A. Pérez-Sato; V. Morales-Ramos; J. J. Bello-Bello (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Effects of feeding ground pods of Enterolobium cyclocarpum Jacq. Griseb on dry matter intake, rumen fermentation, and enteric methane production by Pelibuey sheep fed tropical grass - S. Albores-Moreno; J. A. Alayón-Gamboa; A. J. Ayala-Burgos; F. J. Solorio-Sánchez; C. F. Aguilar-Pérez; L. Olivera-Castillo; J. C. Ku-Vera (Tropical Animal Health and Production, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Tannins and mimosine in Leucaena genotypes and their relations to Leucaena resistance against Leucaena Psyllid and Onion thrips - Ahmed M. M. Ahmed; Francisco J. Solorio Sánchez; Luis Ramírez y Avilés; Rasha Ezzat Elsaid Mahdy; J. B. Castillo Camaal (Agroforestry Systems, 2017)

Indigenous peoples, local communities and climate change mitigation - Ameyali Ramos-Castillo; Edwin J. Castellanos; Kirsty Galloway McLean (Climatic Change, 2017)

Impact of Teratosphaeria nubilosa over tree growth and survival of Eucalyptus globulus and Eucalyptus maidenii in Uruguay - Gustavo Balmelli; Sofía Simeto; Diego Torres; Andrés Hirigoyen; Alicia Castillo; Nora Altier; Guillermo Pérez; Julio J. Diez (New Forests, 2016)

Carboxyl terminus-truncated α1D-adrenoceptors inhibit the ERK pathway - Marco A. Alfonzo-Méndez; Jean A. Castillo-Badillo; M. Teresa Romero-Ávila; Richard Rivera; Jerold Chun; J. Adolfo García-Sáinz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Variation in tussock architecture of the invasive cordgrass Spartina densiflora along the Pacific Coast of North America - Jesús M. Castillo; Brenda J. Grewell; Andrea J. Pickart; Enrique Figueroa; Mark Sytsma (Biological Invasions, 2016)

Phenotypic plasticity and population differentiation in response to salinity in the invasive cordgrass Spartina densiflora - Brenda J. Grewell; Jesús M. Castillo; Meghan J. Skaer Thomason; Rebecca E. Drenovsky (Biological Invasions, 2016)

Analysis of extreme rainfall in the Ebre Observatory (Spain) - Núria Pérez-Zanón; M. Carmen Casas-Castillo; Raúl Rodríguez-Solà; Juan Carlos Peña; Anna Rius; J. Germán Solé; Ángel Redaño (Theoretical and Applied Climatology, 2016)

Drivers of fluorescent dissolved organic matter in the global epipelagic ocean - T. S. Catalá; X. A. Álvarez‐Salgado; J. Otero; F. Iuculano; B. Companys; B. Horstkotte; C. Romera‐Castillo; M. Nieto‐Cid; M. Latasa; X. A. G. Morán; J. M. Gasol; C. Marrasé; et al. (Limnology and Oceanography, 2016)
Fluorescent dissolved organic matter (FDOM) in open surface waters ( 70%) than for the amino acid‐like components ( a . Positive non‐linear relationships between both predictor variables and the two humic‐like PARAFAC components suggest that their distribution are biologically controlled. Compared with the dark ocean (> 200 m), the relationships of C1 and C2 with AOU indicate a higher C1/AOU and C2/AOU ratios of the humic‐like substances in the dark ocean than in the surface ocean where a net effect of photobleaching is also detected. C3 (tryptophan‐like) and C4 (tyrosine‐like) variability was mostly dictated by salinity ( S ), by means of positive non‐linear relationships, suggesting a primary physical control of their distributions at the global surface ocean scale that could be related to the changing evaporation‐precipitation regime. Remarkably, bacterial biomass (BB) only contributed to explain a minor part of the variability of C1 and C4.

Sampling method evaluation and empirical model fitting for count data to estimate densities of Oligonychus perseae (Acari: Tetranychidae) on ‘Hass’ avocado leaves in southern California - Jesús R. Lara; Naseem T. Saremi; Martin J. Castillo; Mark S. Hoddle (Experimental and Applied Acarology, 2016)

Implementation of an experimental nutrient film technique-type aquaponic system - D. Castillo-Castellanos; I. Zavala-Leal; J. M. J. Ruiz-Velazco; A. Radilla-García; J. T. Nieto-Navarro; C. A. Romero-Bañuelos; J. González-Hernández (Aquaculture International, 2016)

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

Antioxidant and toxicological evaluation of a Tamarindus indica L. leaf fluid extract - J.C. Escalona-Arranz; R. Perez-Rosés; J. Rodríguez-Amado; H.J. Morris-Quevedo; L.B. Mwasi; O. Cabrera-Sotomayor; R. Machado-García; O. Fong-Lórez; A. Alfonso-Castillo; E. Puente-Zapata (Natural Product Research, 2016)

Utilizing an Ingestible Biosensor to Assess Real-Time Medication Adherence - Peter R. Chai; Jose Castillo-Mancilla; Eric Buffkin; Chad Darling; Rochelle K. Rosen; Keith J. Horvath; Edwin D. Boudreaux; Gregory K. Robbins; Patricia L. Hibberd; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Physical, chemical, and management-related drivers of submerged macrophyte occurrence in Mediterranean farm ponds - Irene Gallego; Carmen Pérez-Martínez; Pedro M. Sánchez-Castillo; Francisca Fuentes-Rodríguez; Melchor Juan; J. Jesús Casas (Hydrobiologia, 2015)

Closing the gaps on the viral photosystem‐ I psa DCAB gene organization - Sheila Roitman; José Flores‐Uribe; Alon Philosof; Ben Knowles; Forest Rohwer; J. Cesar Ignacio‐Espinoza; Matthew B. Sullivan; Francisco M. Cornejo‐Castillo; Pablo Sánchez; Silvia G. Acinas; Chris L. Dupont; Oded Béjà (Environmental Microbiology, 2015)
Summary Marine photosynthesis is largely driven by cyanobacteria, namely S ynechococcus and P rochlorococcus . Genes encoding for photosystem ( PS ) I and II reaction centre proteins are found in cyanophages and are believed to increase their fitness. Two viral PSI gene arrangements are known, psaJF→ C →A→ B → K → E → D and psaD→ C →A→ B . The shared genes between these gene cassettes and their encoded proteins are distinguished by %G + C and protein sequence respectively. The data on the psaD→ C →A→ B gene organization were reported from only two partial gene cassettes coming from Global Ocean Sampling stations in the P acific and I ndian oceans. Now we have extended our search to 370 marine stations from six metagenomic projects. Genes corresponding to both PSI gene arrangements were detected in the P acific, I ndian and A tlantic oceans, confined to a strip along the equator (30°N and 30°S). In addition, we found that the predicted structure of the viral PsaA protein from the psaD→ C → A → B organization contains a lumenal loop conserved in PsaA proteins from S ynechococcus , but is completely absent in viral PsaA proteins from the psaJF→ C → A → B → K → E → D gene organization and most P rochlorococcus strains. This may indicate a co‐evolutionary scenario where cyanophages containing either of these gene organizations infect cyanobacterial ecotypes biogeographically restricted to the 30°N and 30°S equatorial strip.

Predictive classification of self-paced upper-limb analytical movements with EEG - Jaime Ibáñez; J. I. Serrano; M. D. del Castillo; J. Minguez; J. L. Pons (Medical & Biological Engineering & Computing, 2015)

Anaerobic digestates from vinasse promote growth and lipid enrichment in Neochloris oleoabundans cultures - Eugenia J. Olguín; Efraín Dorantes; Omar S. Castillo; Víctor J. Hernández-Landa (Journal of Applied Phycology, 2015)

Nonlinear relationship between waist to hip ratio, weight and strength in elders: is gender the key? - Carmen Castillo; José A. Carnicero; Mari Ángeles de la Torre; Solange Amor; Amelia Guadalupe-Grau; Leocadio Rodríguez-Mañas; Francisco J. García-García (Biogerontology, 2015)

Chemical modification of Byrsonima crassifolia with citric acid for the competitive sorption of heavy metals from water - J. Monroy-Figueroa; D. I. Mendoza-Castillo; A. Bonilla-Petriciolet; M. A. Pérez-Cruz (International Journal of Environmental Science and Technology, 2015)

Validation of clinical prognostic indices for diffuse large B-cell lymphoma in the National Cancer Data Base - Adam J. Olszewski; Eric S. Winer; Jorge J. Castillo (Cancer Causes & Control, 2015)

Spinal cord toxoplasmosis in human immunodeficiency virus infection/acquired immunodeficiency syndrome - Concepción García-García; Federico Castillo-Álvarez; José M. Azcona-Gutiérrez; María J. Herraiz; Valvanera Ibarra; José A. Oteo (Infectious Diseases, 2015)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Biochemical, Physical, Chemical, and Microbiological Assessment of Blue Shrimp ( Litopenaeus stylirostris ) Stored in Ice - Dalila F. Canizales-Rodríguez; Víctor M. Ocaño-Higuera; Enrique Marquez-Rios; Abril Z. Graciano-Verdugo; Jose L. Cárdenas-López; María S. Yepiz-Gómez; Francisco J. Castillo-Yáñez (Journal of Aquatic Food Product Technology, 2015)

The Aluminum Cryo-plate Increases Efficiency of Cryopreservation Protocols for Potato Shoot Tips - Shin-ichi Yamamoto; Wunna; Tariq Rafique; Miriam Valle Arizaga; Kuniaki Fukui; Esmeralda J. Cruz Gutierrez; Carlos R. Castillo Martinez; Kazuo Watanabe; Takao Niino (American Journal of Potato Research, 2015)

Foraging ecology of silky sharks, Carcharhinus falciformis, captured by the tuna purse-seine fishery in the eastern Pacific Ocean - Leanne M. Duffy; Robert J. Olson; Cleridy E. Lennert-Cody; Felipe Galván-Magaña; Noemi Bocanegra-Castillo; Petra M. Kuhnert (Marine Biology, 2015)

Nuclear translocation of p19INK4d in response to oxidative DNA damage promotes chromatin relaxation - Silvina V. Sonzogni; María F. Ogara; Daniela S. Castillo; Pablo F. Sirkin; J. Pablo Radicella; Eduardo T. Cánepa (Molecular and Cellular Biochemistry, 2015)

Injury of the Developing Cerebellum: A Brief Review of the Effects of Endotoxin and Asphyxial Challenges in the Late Gestation Sheep Fetus - Lisa C. Hutton; Edwin Yan; Tamara Yawno; Margie Castillo-Melendez; Jon J. Hirst; David W. Walker (The Cerebellum, 2014)

Secretion of biologically active human interleukin 22 (IL-22) by Lactococcus lactis - María J. Loera-Arias; Julio Villatoro-Hernández; Miguel A. Parga-Castillo; Alejandro Salcido-Montenegro; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Roberto Montes-de-Oca-Luna; Odila Saucedo-Cárdenas (Biotechnology Letters, 2014)

Aerobiological study in the Mexico City subway system - O. Hernández-Castillo; V. Mugica-Álvarez; M. T. Castañeda-Briones; J. M. Murcia; F. García-Franco; Y. Falcón Briseño (Aerobiologia, 2014)

Effectiveness of the Aquatic Halophyte Sarcocornia perennis spp. perennis as a Biotool for Ecological Restoration of Salt Marshes - Guillermo Curado; Brenda J. Grewell; Enrique Figueroa; Jesús M. Castillo (Water, Air, & Soil Pollution, 2014)

Decadal trends in the pollinator assemblage of Eucryphia cordifolia in Chilean rainforests - Cecilia Smith-Ramírez; Rodrigo Ramos-Jiliberto; Fernanda S. Valdovinos; Paula Martínez; Jessica A. Castillo; Juan J. Armesto (Oecologia, 2014)

Metal ion remediation by polyamidoamine dendrimers: a comparison of metal ion, oxidation state, and titania immobilization - V. A. Castillo; M. A. Barakat; M. H. Ramadan; H. L. Woodcock; J. N. Kuhn (International Journal of Environmental Science and Technology, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

A novel begomovirus isolated from sida contains putative cis- and trans-acting replication specificity determinants that have evolved independently in several geographical lineages - J. A. Mauricio-Castillo; S. I. Torres-Herrera; Y. Cárdenas-Conejo; G. Pastor-Palacios; J. Méndez-Lozano; G. R. Argüello-Astorga (Archives of Virology, 2014)

Partial characterisation of digestive proteases of the Mayan cichlid Cichlasoma urophthalmus - C. A. Cuenca-Soria; C. A. Álvarez-González; J. L. Ortiz-Galindo; H. Nolasco-Soria; D. Tovar-Ramírez; R. Guerrero-Zárate; A. Castillo-Domínguez; M. A. Perera-García; R. Hernández-Gómez; E. Gisbert (Fish Physiology and Biochemistry, 2014)

Spatial patterns of neutral and functional genetic variations reveal patterns of local adaptation in raccoon ( P rocyon lotor ) populations exposed to raccoon rabies - Christopher J. Kyle; Yessica Rico; Sarrah Castillo; Vythegi Srithayakumar; Catherine I. Cullingham; Bradley N. White; Bruce A. Pond (Molecular Ecology, 2014)
Local adaptation is necessary for population survival and depends on the interplay between responses to selective forces and demographic processes that introduce or retain adaptive and maladaptive attributes. Host–parasite systems are dynamic, varying in space and time, where both host and parasites must adapt to their ever‐changing environment in order to survive. We investigated patterns of local adaptation in raccoon populations with varying temporal exposure to the raccoon rabies virus ( RRV ). RRV infects approximately 85% of the population when epizootic and has been presumed to be completely lethal once contracted; however, disease challenge experiments and varying spatial patterns of RRV spread suggest some level of immunity may exist. We first assessed patterns of local adaptation in raccoon populations along the eastern seaboard of N orth A merica by contrasting spatial patterns of neutral (microsatellite loci) and functional, major histocompatibility complex ( MHC ) genetic diversity and structure. We explored variation of MHC allele frequencies in the light of temporal population exposure to RRV (0–60 years) and specific RRV strains in infected raccoons. Our results revealed high levels of MHC variation (66 DRB exon 2 alleles) and pronounced genetic structure relative to neutral microsatellite loci, indicative of local adaptation. We found a positive association linking MHC genetic diversity and temporal RRV exposure, but no association with susceptibility and resistance to RRV strains. These results have implications for landscape epidemiology studies seeking to predict the spread of RRV and present an example of how population demographics influence the degree to which populations adapt to local selective pressures.

Low dispersive modeling of Rayleigh waves on partly staggered grids - O. Rojas; B. Otero; J. E. Castillo; S. M. Day (Computational Geosciences, 2014)

Enhancing Antibacterial Activity Against Escherichia coli K-12 of Peptide Ib-AMP4 with Synthetic Analogues - J. M. Flórez-Castillo; Mercedes Perullini; Matias Jobbágy; Herminsul de Jesús Cano Calle (International Journal of Peptide Research and Therapeutics, 2014)

Inter-specific competition and management modify the morphology, nutrient content and resorption in Scots pine needles - Irantzu Primicia; J. Bosco Imbert; M. Carmen Traver; Federico J. Castillo (European Journal of Forest Research, 2014)

Stomach contents of cetaceans in the Alboran Sea and Gulf of Cadiz. - Garcia-Polo M.; Gimenez Joan; Mons J. Luis; Castillo Juan Jos; De Stephanis R; Santos M.B.; Fernndez Maldonado Carolina (Frontiers in Marine Science, 2014)

Diverging drought-tolerance strategies explain tree species distribution along a fog-dependent moisture gradient in a temperate rain forest - Beatriz Salgado Negret; Fernanda Pérez; Lars Markesteijn; Mylthon Jiménez Castillo; Juan J. Armesto (Oecologia, 2013)

Freshwater biodiversity in the rivers of the Mediterranean Basin - J. Manuel Tierno de Figueroa; Manuel J. López-Rodríguez; Stefano Fenoglio; Pedro Sánchez-Castillo; Romolo Fochetti (Hydrobiologia, 2013)

Are Chileans exposed to dietary furan? - María S. Mariotti; Carla Toledo; Karen Hevia; J. Pablo Gomez; Arvid Fromberg; Kit Granby; Jaime Rosowski; Oscar Castillo; Franco Pedreschi (Food Additives & Contaminants: Part A, 2013)

Native plant restoration combats environmental change: development of carbon and nitrogen sequestration capacity using small cordgrass in European salt marshes - Guillermo Curado; Alfredo E. Rubio-Casal; Enrique Figueroa; Brenda J. Grewell; Jesús M. Castillo (Environmental Monitoring and Assessment, 2013)

IL2/IL21 region polymorphism influences response to rituximab in systemic lupus erythematosus patients - Ana Márquez; Cristina Lucía Dávila-Fajardo; Gema Robledo; José Luis Callejas Rubio; Enrique de Ramón Garrido; Francisco J. García-Hernández; Rocío González-León; Raquel Ríos-Fernández; José Cabeza Barrera; Ma. Francisca González-Escribano; Ma. Teresa Camps García; Ma. Jesús Castillo Palma; et al. (Molecular Biology Reports, 2013)

Multiple domestications of the Mesoamerican gene pool of lima bean (Phaseolus lunatus L.): evidence from chloroplast DNA sequences - R. H. Andueza-Noh; M. L. Serrano-Serrano; M. I. Chacón Sánchez; I. Sanchéz del Pino; L. Camacho-Pérez; J. Coello-Coello; J. Mijangos Cortes; D. G. Debouck; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2013)

Effects of thinning and canopy type on growth dynamics of Pinus sylvestris: inter-annual variations and intra-annual interactions with microclimate - Irantzu Primicia; J. Julio Camarero; J. Bosco Imbert; Federico J. Castillo (European Journal of Forest Research, 2013)

Population structure, habitat features and genetic structure of managed red deer populations - J. Pérez-González; A. C. Frantz; J. Torres-Porras; L. Castillo; J. Carranza (European Journal of Wildlife Research, 2012)

Time to positivity of blood culture association with clinical presentation, prognosis and ESBL-production in Escherichia coli bacteremia - R. Álvarez; L. Viñas-Castillo; J. A. Lepe-Jiménez; E. García-Cabrera; J. M. Cisneros-Herreros (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A new strain of tomato severe leaf curl virus and a unique variant of tomato yellow leaf curl virus from Mexico - B. Bañuelos-Hernández; J. A. Mauricio-Castillo; Y. Cardenas-Conejo; R. G. Guevara-González; G. R. Arguello-Astorga (Archives of Virology, 2012)

Evaluation of four phenotypic methods to detect plasmid-mediated AmpC β-lactamases in clinical isolates - M. J. Gude; C. Seral; Y. Sáenz; M. González-Domínguez; C. Torres; F. J. Castillo (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evaluation of an immunochromatographic dip strip test for simultaneous detection of Cryptosporidium spp, Giardia duodenalis, and Entamoeba histolytica antigens in human faecal samples - P. Goñi; B. Martín; M. Villacampa; A. García; C. Seral; F. J. Castillo; A. Clavel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Sensory changes related to breeding for plant architecture and resistance to viruses and anthracnose in bean market class Fabada (Phaseolus vulgaris L.) - J. J. Ferreira; Romero R. del Castillo; E. Perez-Vega; M. Plans; J. Simó; F. Casañas (Euphytica, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Size, shape and hue modulate attraction and landing responses of the braconid parasitoid Fopius arisanus to fruit odour-baited visual targets - Jeanneth Pérez; Julio C. Rojas; Pablo Montoya; Pablo Liedo; Francisco J. González; Alfredo Castillo (BioControl, 2012)

Evidence for evolutionary convergence at MHC in two broadly distributed mesocarnivores - Vythegi Srithayakumar; Sarrah Castillo; Julien Mainguy; Christopher J. Kyle (Immunogenetics, 2012)

Development of wild barley (Hordeum chilense)-derived DArT markers and their use into genetic and physical mapping - C. Rodríguez-Suárez; M. J. Giménez; N. Gutiérrez; C. M. Ávila; A. Machado; E. Huttner; M. C. Ramírez; A. C. Martín; A. Castillo; A. Kilian; A. Martín; S. G. Atienza (Theoretical and Applied Genetics, 2012)

Detection and characterization of a ST6 clone of vanB2-Enterococcus faecalis from three different hospitals in Spain - M. López; A. Rezusta; C. Seral; C. Aspiroz; C. Marne; M. J. Aldea; I. Ferrer; M. J. Revillo; F. J. Castillo; C. Torres (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Wholesale replacement of lima bean (Phaseolus lunatus L.) landraces over the last 30 years in northeastern Campeche, Mexico - J. Martínez-Castillo; L. Camacho-Pérez; J. Coello-Coello; R. Andueza-Noh (Genetic Resources and Crop Evolution, 2012)

Assessment of Metal Pollution in Soils From a Former Havana (Cuba) Solid Waste Open Dump - O. Díaz Rizo; M. Hernández Merlo; F. Echeverría Castillo; J. O. Arado López (Bulletin of Environmental Contamination and Toxicology, 2012)

Bicarbonate ingestion has no ergogenic effect on consecutive all out sprint tests in BMX elite cyclists - Mikel Zabala; Ana B. Peinado; Francisco J. Calderón; Javier Sampedro; Manuel J. Castillo; Pedro J. Benito (European Journal of Applied Physiology, 2011)

Inexorable spread: inexorable death? The fate of neo-XY chromosomes of grasshoppers - CLAUDIO J. BIDAU; DARDO A. MARTÍ; ELIO R. CASTILLO (Journal of Genetics, 2011)

High genetic variability and recombination in a begomovirus population infecting the ubiquitous weed Cleome affinis in northeastern Brazil - Sarah J. C. da Silva; Gloria P. Castillo-Urquiza; Braz T. Hora Júnior; Iraildes P. Assunção; Gaus S. A. Lima; Gilvan Pio-Ribeiro; Eduardo S. G. Mizubuti; F. Murilo Zerbini (Archives of Virology, 2011)

Effect of fitness and physical activity on bone mass in adolescents: the HELENA Study - L. Gracia-Marco; G. Vicente-Rodríguez; J. A. Casajús; D. Molnar; M. J. Castillo; L. A. Moreno (European Journal of Applied Physiology, 2011)

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Assessment of Heavy Metal Pollution in Urban Soils of Havana City, Cuba - O. Díaz Rizo; F. Echeverría Castillo; J. O. Arado López; M. Hernández Merlo (Bulletin of Environmental Contamination and Toxicology, 2011)

The Uptake of Copper by Aldama dentata: Ecophysiological Response, Its Modeling, and the Implication for Phytoremediation - N. Dasgupta-Schubert; M. G. Barrera; C. J. Alvarado; O. S. Castillo; E. M. Zaragoza; S. Alexander; S. Landsberger; S. Robinson (Water, Air, & Soil Pollution, 2011)

Isolation of the new anacardic acid 6-[16′Z-nonadecenyl]-salicylic acid and evaluation of its antimicrobial activity against Streptococcus mutans and Porphyromonas gingivalis - Blanca E. Rivero-Cruz; Nuria Esturau; Sobeida Sánchez-Nieto; Irma Romero; Israel Castillo-Juárez; J. Fausto Rivero-Cruz (Natural Product Research, 2011)

Effect of increasing levels of white mulberry leaves (Morus alba) on ruminal dry matter degradability in lambs - Jaime Salinas-Chavira; Omar Castillo-Martínez; J. Efren Ramirez-Bribiesca; Miguel Mellado (Tropical Animal Health and Production, 2011)

Algal assemblages and their relationship with water quality in tropical Mexican streams with different land uses - G. Vázquez; J. A. Aké-Castillo; M. E. Favila (Hydrobiologia, 2011)

MHC class II DRB diversity in raccoons (Procyon lotor) reveals associations with raccoon rabies virus (Lyssavirus) - Vythegi Srithayakumar; Sarrah Castillo; Rick C. Rosatte; Christopher J. Kyle (Immunogenetics, 2011)

Microsatellite loci for the blue swimming crab (Callinectes bellicosus) (Crustacea: Portunidae) from the Gulf of California, Mexico - A. Munguia-Vega; J. Torre; A. Castillo-Lopez; T. Pfister; R. Cudney-Bueno (Conservation Genetics Resources, 2010)

Influence of nutrients, submerged macrophytes and zooplankton grazing on phytoplankton biomass and diversity along a latitudinal gradient in Europe - Koenraad Muylaert; Carmen Pérez-Martínez; Pedro Sánchez-Castillo; Torben L. Lauridsen; Maarten Vanderstukken; Steven A. J. Declerck; Katleen Van der Gucht; José-Maria Conde-Porcuna; Erik Jeppesen; Luc De Meester; Wim Vyverman (Hydrobiologia, 2010)

Sleep patterns in Spanish adolescents: associations with TV watching and leisure-time physical activity - Francisco B. Ortega; Palma Chillón; Jonatan R. Ruiz; Manuel Delgado; Ulrike Albers; Jesús L. Álvarez-Granda; Ascensión Marcos; Luis A. Moreno; Manuel J. Castillo (European Journal of Applied Physiology, 2010)

Effect of dietary protein source and time on alkaline proteolytic activity of Nile tilapia (Oreochromis niloticus) - Mayra L. González-Félix; Francisco J. Castillo-Yañez; Víctor M. Ocaño-Higuera; Martin Perez-Velazquez; Venecia Cota-Moreno; José Lozano-Taylor (Fish Physiology and Biochemistry, 2010)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Neo-sex chromosome diversity in Neotropical melanopline grasshoppers (Melanoplinae, Acrididae) - Elio R. D. Castillo; Claudio J. Bidau; Dardo A. Martí (Genetica, 2010)

Consilience of genetics and archaeobotany in the entangled history of rice - Dorian Q. Fuller; Yo-Ichiro Sato; Cristina Castillo; Ling Qin; Alison R. Weisskopf; Eleanor J. Kingwell-Banham; Jixiang Song; Sung-Mo Ahn; Jacob van Etten (Archaeological and Anthropological Sciences, 2010)

Estimation of tropical forest structure from SPOT-5 satellite images - Miguel Angel Castillo-Santiago; Martin Ricker; Bernardus H. J. de Jong (International Journal of Remote Sensing, 2010)

Coral reefs of the Pacific coast of Nicaragua - J. J. Alvarado; H. Reyes-Bonilla; F. Buitrago; J. Aguirre-Rubí; P. A. Álvarez del Castillo Cardenas (Coral Reefs, 2010)

Poly-β-Hydroxyalkanoate Exert a Protective Effect Against Carbon Starvation and Frozen Conditions in Sphingopyxis chilensis - P. Pavez; J. L. Castillo; C. González; Miguel Martínez (Current Microbiology, 2009)

Climbing time to exhaustion is a determinant of climbing performance in high-level sport climbers - Vanesa España-Romero; Francisco B. Ortega Porcel; Enrique G. Artero; David Jiménez-Pavón; Ángel Gutiérrez Sainz; Manuel J. Castillo Garzón; Jonatan R. Ruiz (European Journal of Applied Physiology, 2009)

Monthly variation in the chemical composition of Eisenia arborea J.E. Areschoug - Gustavo Hernández-Carmona; Silvia Carrillo-Domínguez; Dora Luz Arvizu-Higuera; Y. Elizabeth Rodríguez-Montesinos; J. Iván Murillo-Álvarez; Mauricio Muñoz-Ochoa; Rosa María Castillo-Domínguez (Journal of Applied Phycology, 2009)

Microspore embryogenesis: assignment of genes to embryo formation and green vs. albino plant production - M. Muñoz-Amatriaín; J. T. Svensson; A. M. Castillo; T. J. Close; M. P. Vallés (Functional & Integrative Genomics, 2009)

Functional analysis of a large non-conserved region of FlgK (HAP1) from Rhodobacter sphaeroides - David J. Castillo; Teresa Ballado; Laura Camarena; Georges Dreyfus (Antonie van Leeuwenhoek, 2009)

Pre-diagnosis body mass index, post-diagnosis weight change, and prognosis among women with early stage breast cancer - Bette J. Caan; Marilyn L. Kwan; Georgina Hartzell; Adrienne Castillo; Martha L. Slattery; Barbara Sternfeld; Erin Weltzien (Cancer Causes & Control, 2008)

Strontium Levels in Different Causes of Death: Diagnostic Efficacy in Drowning - M. D. Pérez-Cárceles; A. Sibón; M. L. Gil del Castillo; M. A. Vizcaya; E. Osuna; T. Casas; J. L. Romero; A. Luna (Biological Trace Element Research, 2008)

Plant zonation at salt marshes of the endangered cordgrass Spartina maritima invaded by Spartina densiflora - Jesús M. Castillo; Enrique Mateos-Naranjo; Francisco J. Nieva; Enrique Figueroa (Hydrobiologia, 2008)

Genetic erosion and in situ conservation of Lima bean (Phaseolus lunatus L.) landraces in its Mesoamerican diversity center - J. Martínez-Castillo; P. Colunga-GarcíaMarín; D. Zizumbo-Villarreal (Genetic Resources and Crop Evolution, 2008)

Phenotypic plasticity blurs ecotypic divergence in the response of Quercus coccifera and Pinus halepensis to water stress - Francisco J. Baquedano; Fernando Valladares; Federico J. Castillo (European Journal of Forest Research, 2008)

Immunological changes after a single bout of moderate-intensity exercise in a hot environment - J. Romeo; D. Jiménez-Pavón; M. Cervantes-Borunda; J. Wärnberg; S. Gómez-Martínez; M. J. Castillo; A. Marcos (Journal of Physiology and Biochemistry, 2008)

Binding of mismatch repair protein MutS to mispaired DNA adducts of intercalating ruthenium(II) arene complexes - Maria Castellano-Castillo; Hana Kostrhunova; Victoria Marini; Jana Kasparkova; Peter J. Sadler; Jean-Marc Malinge; Viktor Brabec (JBIC Journal of Biological Inorganic Chemistry, 2008)

Comparative response of bread and durum wheat cultivars to nitrogen fertilizer in a rainfed Mediterranean environment: soil nitrate and N uptake and efficiency - Rafael J. López-Bellido; Juan E. Castillo; Luis López-Bellido (Nutrient Cycling in Agroecosystems, 2008)

Correlation between the presence of symptoms and the Giardia duodenalis genotype - J. Sahagún; A. Clavel; P. Goñi; C. Seral; M. T. Llorente; F. J. Castillo; S. Capilla; A. Arias; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Suitability of weed species prevailing in Spanish vineyards as hosts for root-knot nematodes - P. Castillo; H. F. Rapoport; J. E. Palomares Rius; R. M. Jiménez Díaz (European Journal of Plant Pathology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Carbon emissions from land-use change: an analysis of causal factors in Chiapas, Mexico - M. A. Castillo-Santiago; A. Hellier; R. Tipper; B. H. J. de Jong (Mitigation and Adaptation Strategies for Global Change, 2007)

Correlations between sea‐surface temperatures and warm season streamflow in northwest Mexico - David J. Gochis; Luis Brito‐Castillo; W. James Shuttleworth (International Journal of Climatology, 2007)
Previous hydroclimatological analysis of the North American Monsoon (NAM) region of northwest México revealed significant sub‐regions of coherence in seasonal precipitation and streamflow. In this work, interannual variations in regionalized streamflow and rainfall‐runoff relationships are explored. Modulation of the monsoon hydroclimatology by large‐scale forcing mechanisms such as tropical, North Pacific, and Caribbean Sea‐surface temperature perturbations results in nonlinear responses in seasonal runoff that varies by region. Analyses reveal that the El Niño‐Southern Oscillation (ENSO) exerts a modest but statistically significant influence on NAM streamflow. Different sea‐surface temperature and sea‐level pressure indices exhibit markedly different lag‐correlation structures in different NAM streamflow regions and these relationships vary significantly according to the decadal scale sea‐surface temperature (SST) variability in the North Pacific. The structure of correlation patterns between eastern Pacific SST and regionalized NAM streamflow anomalies complicates the application of common ENSO indices as streamflow predictors. The occurrence of ENSO also has a significant impact on regional runoff fractions and on the partitioning of streamflow between the summer and winter seasons. The summer ENSO influence is explained, in part, by changes in the lower tropospheric pressure and wind fields, which result in modest increases in atmospheric moisture over the streamflow regions during La Niña episodes versus El Niño episodes. The results suggest that improved monitoring and prediction of ENSO variability, through careful development of eastern Pacific SST indices in the pre‐monsoon period should provide useful guidance for seasonal forecasts of regional monsoon streamflow. Copyright © 2006 Royal Meteorological Society

Identification of Pratylenchus thornei, the cereal and legume root-lesion nematode, based on SCAR-PCR and satellite DNA - S. Carrasco-Ballesteros; P. Castillo; B. J. Adams; E. Pérez-Artés (European Journal of Plant Pathology, 2007)

The cyanotrophic bacterium Pseudomonas pseudoalcaligenes CECT5344 responds to cyanide by defence mechanisms against iron deprivation, oxidative damage and nitrogen stress - Victor M. Luque‐Almagro; María J. Huertas; M. Dolores Roldán; Comrado Moreno‐Vivián; Manuel Martínez‐Luque; Rafael Blasco; Francisco Castillo (Environmental Microbiology, 2007)
Summary Two‐dimensional (2‐D) electrophoresis approach has been used to test protein expression changes in response to cyanide in the alkaliphilic bacterium Pseudomonas pseudoalcaligenes CECT5344. This is a cyanide‐assimilating strain which also grows in media containing cyanide‐enriched effluent from the jewellery industry. The bacterium efficiently uses this residue as the sole nitrogen source for aerobic growth under alkaline pH with negligible nitrogen losses as HCN. Cell‐free extracts isolated from P. pseudoalcaligenes grown with a jewellery residue, free cyanide or ammonium chloride as nitrogen source were subjected to 2‐D electrophoresis and the spot patterns were examined to determine differential protein expression. Electrophoretic plates exhibiting an average of 1000 spots showed significant differences in the expression of about 44 proteins depending on the nitrogen source. Some of these protein spots were analysed by Matrix‐assisted laser desorption/ionization‐time of flight‐mass spectrometry (MALDI‐TOF‐MS). Characterization of five of these proteins reveals that cyanide shock induces proteins related to iron acquisition, regulation of nitrogen assimilation pathways and oxidative stress repairing and protection.

Interguanine hydrogen-bonding patterns in adducts with water and Zn–purine complexes (purine is 9-methyladenine and 9-methylguanine). Unexpected preference of Zn(II) for adenine-N7 over guanine-N7 - Pilar Amo-Ochoa; Pablo J. Sanz Miguel; Oscar Castillo; Michal Sabat; Bernhard Lippert; Félix Zamora (JBIC Journal of Biological Inorganic Chemistry, 2007)

Complete sequence of the RNA1 of a European isolate of tomato chlorosis virus - G. Lozano; E. Moriones; J. Navas-Castillo (Archives of Virology, 2007)

Introgression in the genus Salmo via allotriploids - A. G. F. CASTILLO; E. BEALL; P. MORAN; J. L. MARTINEZ; F. AYLLON; E. GARCIA‐VAZQUEZ (Molecular Ecology, 2007)
Hybridization between sympatric species is not uncommon in the wild. Wild allotriploids (individuals with two chromosome sets from a species + one chromosome set from another species) are generally the result of a backcross between interspecific hybrids that produce unreduced gametes and one of the parental species. In animals, allotriploids are commonly sterile, except for some vertebrate species complexes in which allotriploids reproduce by parthenogenesis, gynogenesis and/or hybridogenesis, producing generally clonal or hemiclonal gametes; nuclear DNA introgression between hybridizing species is considered to be extremely rare. Employing species‐specific molecular markers, we show genetic introgression between the chromosomally well‐differentiated salmonids Atlantic salmon (2n = 58) and brown trout (2 n = 80) through spontaneous bisexual reproduction of allotriploids leading to salmon‐like offspring bearing some brown trout genes. Although introgression between these Salmo species can occur via allotriploids, we hypothesize that extinction of parental species can be discarded based on very low survival of allotriploid offspring.

Cinnamtannin B-1 from bay wood exhibits antiapoptotic effects in human platelets - A. Bouaziz; C. Romera-Castillo; S. Salido; P. J. Linares-Palomino; J. Altarejos; A. Bartegi; J. A. Rosado; G. M. Salido (Apoptosis, 2007)

Prevalence of fecal carriage of ESBL-producing Enterobacteriaceae in hospitalized and ambulatory patients during two non-outbreak periods - F. J. Castillo García; C. Seral García; M. P. Gandara; M. I. Millán Lou; C. Pitart Ferré (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Comparative ecophysiological effects of drought on seedlings of the Mediterranean water-saver Pinus halepensis and water-spenders Quercus coccifera and Quercus ilex - F. J. Baquedano; F. J. Castillo (Trees, 2006)

Influence of Grain Processing on Acid–Base Balance in Feedlot Steers - C. Castillo; J. Hernández; J. Méndez; J. Llena; V. Pereira; M. López-Alonso; J. L. Benedito (Veterinary Research Communications, 2006)

Early effects of tillage and crop rotation on arbuscular mycorrhizal fungal propagules in an Ultisol - C. G. Castillo; R. Rubio; J. L. Rouanet; F. Borie (Biology and Fertility of Soils, 2006)

Expression and characterization of the assimilatory NADH-nitrite reductase from the phototrophic bacterium Rhodobacter capsulatus E1F1 - M. Francisca Olmo-Mira; Purificación Cabello; Carmen Pino; Manuel Martínez-Luque; David J. Richardson; Francisco Castillo; M. Dolores Roldán; Conrado Moreno-Vivián (Archives of Microbiology, 2006)

Production of doubled haploids in durum wheat (Triticum turgidum L.) through isolated microspore culture - L. Cistué; M. Soriano; A. M. Castillo; M. P. Vallés; J. M. Sanz; B. Echávarri (Plant Cell Reports, 2006)

Complete nucleotide sequence of the RNA2 of the crinivirus tomato chlorosis virus - G. Lozano; E. Moriones; J. Navas-Castillo (Archives of Virology, 2006)

Climatic cycles inferred from the aminostratigraphy and aminochronology of Quaternary dunes and palaeosols from the eastern islands of the Canary Archipelago - J. E. Ortiz; T. Torres; Y. Yanes; C. Castillo; J. De La Nuez; M. Ibáñez; M. R. Alonso (Journal of Quaternary Science, 2006)
Aminochronological and aminostratigraphical methods have been used to study the Quaternary aeolian deposits from the islands located east of the Canary Archipelago (Fuerteventura and Lanzarote islands and La Graciosa, Montaña Clara and Alegranza islets). The extent of racemisation/epimerisation of four amino acids (isoleucine, aspartic acid, phenylalanine and glutamic acid) was measured in land snail shells of the genus Theba . The age calculation algorithms of these amino acids have been determined to permit the numerical dating of these deposits. Eight Aminozones, each defining dune/palaeosol‐formation episodes, have been distinguished and dated at 48.6 ± 6.4, 42.5 ± 6.0, 37.8 ± 4.6, 29.4 ± 4.8, 22.4 ± 4.5, 14.9 ± 3.6, 11.0 ± 4.0 and 5.4 ± 1.1 ka BP, the first five of them defining cycles of 5–7 ka. The alternation of palaeosols and aeolian deposits, which are related to abrupt transitions from humid to arid conditions, are the reflection of globally induced changes in North Africa palaeoenvironmental conditions linked to the effect of African palaeomonsoons on the trade winds and the Saharan Air Layer. Probably these aeolian cycles, with a recurrence period of 5–7 ka, are the expression of multiples of the ∼2.4 ka solar‐cycle. Copyright © 2005 John Wiley & Sons, Ltd.

18th International Mouse Genome Conference - Amy C. Lossie; Thomas P. Meehan; Andrew Castillo; Lihua Zheng; Keith C. Weiser; Mark A. Strivens; Monica J. Justice (Mammalian Genome, 2005)

Application of the ‘Climafor’ Approach to Estimate Baseline Carbon Emissions of a Forest Conservation Project in the Selva Lacandona, Chiapas, Mexico - B. H. J. De Jong; A. Hellier; M. A. Castillo-Santiago; R. Tipper (Mitigation and Adaptation Strategies for Global Change, 2005)

Clonal growth and tiller demography of the invader cordgrass Spartina densiflora brongn. At two contrasting habitats in SW European salt marshes - F. Javier J. Nieva; Eloy M. Castellanos; Jesús M. Castillo; M. Enrique Figueroa (Wetlands, 2005)

Short-term responses to salinity of an invasive cordgrass - Jesús M. Castillo; Alfredo E. Rubio-Casal; Susana Redondo; Antonio A. Álvarez-López; Teresa Luque; Carlos Luque; Francisco J. Nieva; Eloy M. Castellanos; Manuel E. Figueroa (Biological Invasions, 2005)

Effect of irrigation method and N-fertilizer management on rice yield, water productivity and nutrient-use efficiencies in typical lowland rice conditions in China - Romeo J. Cabangon; To Phuc Tuong; Ernesto G. Castillo; Lang Xing Bao; Guoan Lu; Guangho Wang; Yuanlai Cui; Bas A. M. Bouman; Yuanhua Li; Chongde Chen; Jianzhang Wang (Paddy and Water Environment, 2004)

Cryptic isolation of Gulf of California shovelnose guitarfish evidenced by mitochondrial DNA - J. Sandoval-Castillo; A. Rocha-Olivares; C. Villavicencio-Garayzar; E. Balart (Marine Biology, 2004)

Ten-Year Viability Study on Natural Populations of Drosophila Sibling Species from Laguna Verde, Veracruz, México - E. Pimentel; M. P. Cruces; V. M. Salceda; M. E. de la Rosa; L. Levine; J. A. Castillo (Archives of Environmental Contamination and Toxicology, 2004)

Arbuscular mycorrhizae of the palm Astrocaryum mexicanum in disturbed and undisturbed stands of a Mexican tropical forest - O. Nez-Castillo; F. J. lvarez-Snchez (Mycorrhiza, 2003)

Random Amplified Polymorphic DNA Profiles as a Tool for the Identification of Acanthamoeba divionensis - Nestor J. Abreu; Pilar Foronda; Antonio del Castillo; Basilio Valladares; Antonio Ortega-Rivas; Jacob Lorenzo-Morales; Violeta Alonso (Current Microbiology, 2003)

Bottom‐up controls on bacterial production in tropical lowland rivers - María M. Castillo; George W. Kling; J. David Allan (Limnology and Oceanography, 2003)
The importance of organic carbon and inorganic nutrients in controlling bacterial production was investigated in two tropical lowland rivers draining undisturbed forested catchments. Glucose (C), ammonium (N), phosphate (P), leaf leachate, and algal leachate were added alone or combined to water collected from one clear‐water (Cataniapo) and one black‐water (Autana) river of the Middle Orinoco basin, and bacterial production (BP) was measured at 0, 8, 24, and 36 h of incubation. The rivers have low pH (3.8–5.9) and conductivity (6.3–9.1 µS cm −1 ) and abundant nitrogen (total N, 273–314 µg L −1 ) compared to phosphorus (total P, 3.6–5.5 µg L −1 ). BP was significantly stimulated by additions of P, CP, NP, and CNP in both river waters. N or C alone or combined did not stimulate BP, suggesting that P rather than carbon is the primary limiting nutrient in these rivers. Higher responses to CNP and CP amendments (3–7 times over controls), compared to P and NP (1.3–4 times over controls), indicate that carbon is an important secondary constraint to bacterial production. Responses to NP and P were more frequent in the Autana than in the Cataniapo, suggesting that bacteria in the clear‐water river were less resource limited than those in the black‐water river. Responses to added leaf leachate, which had high concentrations of P and dissolved organic carbon (DOC), were generally greater than responses to added algal leachate. Seasonal patterns in response to nutrient addition suggest that the size of the labile fraction of DOC may increase during periods of low and rising water.

Insights into Insulin and Glucagon Responses in Fish - I. Navarro; P. Rojas; E. Capilla; A. Albalat; J. Castillo; N. Montserrat; M. Codina; J. Gutiérrez (Fish Physiology and Biochemistry, 2002)

Evaluation of an Immunochromatographic Dip-Strip Test for the Detection of Cryptosporidium Oocysts in Stool Specimens - M. Llorente; A. Clavel; M. Varea; S. Olivera; F. Castillo; J. Sahagún; M. Rubio; R. Gómez-Lus (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Parasitoid diversity and impact on populations of the diamondback moth Plutella xylostella (L.) on Brassica crops in central México - M. Martínez-Castillo; J.L. Leyva; J. Cibrián-Tovar; R. Bujanos-Muñiz (BioControl, 2002)

Genetic loci associated with field resistance to late blight in offspring of Solanum phureja and S.tuberosum grown under short-day conditions - M. Ghislain; B. Trognitz; Ma. del R. Herrera; J. Solis; G. Casallo; C. Vásquez; O. Hurtado; R. Castillo; L. Portal; M. Orrillo (Theoretical and Applied Genetics, 2001)

Nitrogen pollution by dairy cows and its mitigation by dietary manipulation - E. Kebreab; J. France; D.E. Beever; A.R. Castillo (Nutrient Cycling in Agroecosystems, 2001)

Effect of abscisic acid and jasmonic acid on partial desiccation of encapsulated somatic embryos of sugarcane - Nadina Nieves; M. E. Martínez; R. Castillo; María A. Blanco; J. L. González-Olmedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Some properties of semicarbazide-sensitive amine oxidase (SSAO) from human cerebrovascular tissues - C. Smeraldi; V. Castillo; J. M. Lizcano; M. Unzeta (Inflammation Research, 2001)

Efficient production of androgenic doubled-haploid mutants in barley by the application of sodium azide to anther and microspore cultures - A. M. Castillo; L. Cistué; M. P. Vallés; J. M. Sanz; I. Romagosa; J. L. Molina-Cano (Plant Cell Reports, 2001)

Polymorphism of the 5′ terminal region of Citrus tristeza virus (CTV) RNA: Incidence of three sequence types in isolates of different origin and pathogenicity - M. A. Ayllón; C. López; J. Navas-Castillo; S. M. Garnsey; J. Guerri; R. Flores; P. Moreno (Archives of Virology, 2001)

Causes and consequences of salt-marsh erosion in an Atlantic estuary in SW Spain - J. M. Castillo; C. J. Luque; E. M. Castellanos; M. E. Figueroa (Journal of Coastal Conservation, 2000)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

An assessment of genetic relationships within the genus Digitalis based on PCR-generated RAPD markers - S. G. Nebauer; L. del Castillo-Agudo; J. Segura (Theoretical and Applied Genetics, 2000)

Liver injury caused by ebrotidine: a new example of the utility of the postmarketing surveillance - J. R. Castillo; J. Torelló; A. Hernandez (European Journal of Clinical Pharmacology, 2000)

Mercurialis ambigua and Solanum luteum: Two Newly Discovered Natural Hosts of Tomato Yellow Leaf Curl Geminiviruses - S. Sánchez-Campos; J. Navas-Castillo; F. Monci; J.A. Díaz; E. Moriones (European Journal of Plant Pathology, 2000)

Plant species of traditional Mayan homegardens of Mexico as analogs for multistrata agroforests - F. A. J. De Clerck; P. Negreros-Castillo (Agroforestry Systems, 2000)

Investigation of Tuberculosis Contacts in a Nonhospital Pneumology Practice - D. del Castillo Otero; M. Peñafiel Colás; F. Álvarez Gutiérrez; J.G. Soto Campos; E. Calderón Osuna; J. Toral Marín; J. Sánchez Gómez (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

Desiccated doubled-haploid embryos obtained from microspore culture of barley cv. Igri - A. B. Ryan; A. M. Castillo; M. P. Vallés; J. M. Sanz; L. Cistué (Plant Cell Reports, 1999)

RAPD variation within and among natural populations of outcrossing willow-leaved foxglove (Digitalis obscura L.) - S. G. Nebauer; L. del Castillo-Agudo; J. Segura (Theoretical and Applied Genetics, 1999)

Synchronous and early activation of planarian Hox genes and the re-specification of body axes during regeneration in Dugesia (G.) tigrina (Turbellaria; Tricladida) - J. R. Bayascas; E. Castillo; A.M. Muñoz-Mármol; J. Baguñà; E. Saló (Hydrobiologia, 1998)

Use of a Selective Medium and a Membrane Filter Method for Isolation of Campylobacter Species from Spanish Paediatric Patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Somatic embryogenesis and plant regeneration from barley cultivars grown in Spain - A. M. Castillo; B. Egaña; J. M. Sanz; L. Cistué (Plant Cell Reports, 1998)

Use of a selective medium and a membrane filter method for isolation ofCampylobacter species from Spanish paediatric patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Plasma membrane redox system activity in tumour cell lines of mammary origins with different proliferation rates - A. E. del Valle; A. del Castillo-Olivares; F. Sánchez-Jiménez; J. Márquez; I. Núñez de Castro; M. A. Medina (Protoplasma, 1998)

Degradation of p -nitrophenol by the phototrophic bacterium Rhodobacter capsulatus - M. D. Roldán; R. Blasco; F. J. Caballero; F. Castillo (Archives of Microbiology, 1997)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)

Photoinactivation of the detoxifying enzyme nitrophenol reductase from Rhodobacter capsulatus - Rafael Blasco; Pedro J. Aparicio; Francisco Castillo (Archives of Microbiology, 1995)

Photoinactivation of the detoxifying enzyme nitrophenol reductase from Rhodobacter capsulatus - Rafael Blasco; Pedro J. Aparicio; F. Castillo (Archives of Microbiology, 1995)

Ammonia assimilation pathways in Rhodopseudomonas capsulata E1F1 - C. Moreno-Vivin; F. J. Cejudo; J. Crdenas; F. Castillo (Archives of Microbiology, 1983)